GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 192056739 species occurrences available in GBIF matching the query: { "or" : [ "BasisOfRecord is Specimen", "BasisOfRecord is Fossil", "BasisOfRecord is Unknown evidence" ] }. The dataset includes 192056739 records from 13216 constituent datasets: 29 records from Nomenclatural and type catalogue of Athoracophoridae (Mollusca: Eupulmonata: Succineoidea): a synopsis of the first 185 years of biodiscovery in the South West Pacific region. 11961 records from MEXU/Leguminosae. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 2 records from Waldstück Bremerhagen LK Bio Kl. 12. 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 39 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 581 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 50873 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 1971 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 1 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 339 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 2812 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 25 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 878 records from COA Bird Collection (Arctos). 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 10654 records from Bryophyte specimens of The Nagoya University Museum. 4 records from New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae). 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 34520 records from University of Guam Insect Collection. 22857 records from National Botanic Garden Belgium - Myxomycetes. 5 records from Review of the fossil record of Bolitophilidae, with description of new taxa and discussion of position of Mangas Kovalev (Diptera: Sciaroidea). 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 9 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 109 records from Nannofossil abundance of Hole 24-232. 177 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 3072 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche. 1189 records from UWIZM Molluscs. 7 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 265 records from Nannofossil abundance of Hole 36-329. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 382 records from orthopteracollections-nhmj-ioj. 824 records from Bird specimens of Saitama Museum of Natural History. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 9 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 413 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 24370 records from Muséum d'Avignon. 626 records from Mycology collection, Norwegian Forest and Landscape Institute. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 4 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 20 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 7 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 2808 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 55 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 42 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 7 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 173 records from UWIZM Anoles. 10 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 1 records from Nothrus pulverulentus. 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 444 records from Pollen analysis of sediment profile TR0 from Truennensee. 2451 records from Macrobenthos Chukchi Sea, 1986. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 7 records from Tobrilus methanus sp. n. and Tripyla posolskii sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 55 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 425 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 48 records from Tardigrad collection of the National Museum of Nature and Science. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 8 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 599 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 14923 records from Lepidopterous specimens of Yamagata Prefectural Museum. 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 221 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 1 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 1 records from Orthoptera - SMF. 13 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 391 records from An updated checklist of aquatic plants of Myanmar and Thailand. 1702 records from BioGIS - Bryophytes - HUJ collections. 752 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 10 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 672 records from Colección de Entomología - Curculionidae. 6 records from Taxonomy of the European Pied Flycatcher Ficedula hypoleuca (Aves: Muscicapidae). 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 30 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 13 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 3 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 19739 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 3 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 423 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 6237 records from Plecoptera. 52 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 9 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 3 records from Benthic hydroids (Cnidaria: Hydrozoa) from off George V Coast (East Antarctica). 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 14 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 5 records from Redescription and phylogenetic analysis of the type species of the giant pill-millipede genus Sphaeropoeus Brandt, 1833 (Diplopoda, Sphaerotheriida, Zephroniidae). 280 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 34 records from NZCS Brownsberg Nature Park Monitoring. 143 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 67 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 101 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 25 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 24 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 3 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 208 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 1952 records from ISM Ichthyology Collection. 798 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 5 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 1 records from Formiciden aus dem Naturhistorischen Museum in Hamburg. II. Teil. Neueingaenge seit 1900 (PP). 142891 records from The Himalayan Uplands Plant database (HUP Version 1). 1 records from Artenvielfalt auf dem Schulgelände. 31015 records from National Museum of Natural Science. 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 17 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 322 records from Collections ichtyologiques et herpétologiques (BOUM). 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 13 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 65903 records from Norwegian Lepidoptera working group. 26 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 38876 records from Pteridophyta collection of Museum of Natural and Environmental History, Shizuoka. 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 2 records from A new Panolis Hübner, [1821] species from Vietnam (Lepidoptera, Noctuidae, Orthosiini). 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 1014 records from Pollen profile ADR353. 270 records from bmhs_weatherheadshell_collection. 1 records from Sächsische Schweiz (Pfaffenstein). 234 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 285727 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 6 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 220 records from Living Cirripedia. 11 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 9 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 510 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 1 records from Roter Berg Werdau (Leubnitz). 36 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 15 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 7 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 24197 records from University of California Santa Barbara Invertebrate Zoology Collection. 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 2 records from Neue Milbenarten aus Kärnten. 56964 records from Entomology Collection at the Natural History Museum of Utah. 4 records from Four new Megaselia species (Diptera: Phoridae) from animal carcasses in Bangi, Malaysia. 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 6390 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 2 records from A PArtial Skeleton of the Tyrannosaurid Dinosaur Aublysodon from the Upper Cretaceous of New Mexico. 11 records from Visual Plants (144.41.33.158) - Herbarium specimens from "LOJA" Ecuador. 113616 records from ALCB - Herbário Alexandre Leal Costa. 4 records from Ceraeocercus Uvarov, a genus recorded in China for the first time (Orthoptera, Tettigoniidae; Tettigoniinae; Drymadusini). 3184 records from Herbarium specimens of Limoges university (LIMO). 4847 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 105857 records from Fish specimens of Kagoshima University Museum. 233 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 4185 records from Diptera Collection of Museum and Institute of Zoology PAS. 13647 records from UTEP Invertebrates (Arctos). 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 23 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 2 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 998 records from Korean Ethnobotany Database. 163 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 481 records from Herbario MAIA, colección Flora Forestal del INIA-CIFOR. 41 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 23643 records from CNIN/Abejas de México/Apoidea. 1567 records from Flora útil del Municipio de la Huerta, Jalisco. 1726 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 302 records from UF Environmental Archaeology Tick Island Zooarchaeological Data. 116455 records from Naturalis Biodiversity Center (NL) - Crustacea. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 14 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 20627 records from Herbier Louis-Marie (QFA) - Collection de lichens. 607514 records from Plant. 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 169 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 3 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 12859 records from Colecção Entomológica IIA. 17155 records from MZFC/Coleccion de Aves. 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 7116 records from DMNS Egg Collection (Arctos). 2007 records from Plant specimens of Bihoro Museum. 944 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 78 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 6 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 22 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 394 records from Reptilia ZMK. 85277 records from University of Ghana - Ghana Herbarium. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 1943 records from Pollen profile RAC20, Lake Racou, France. 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 3 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10898 records from Inventario de Hymenóptera; parasítica en México. 378 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 22516 records from MfN - Fossil Fish Collection. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 750 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 23 records from Nannofossil abundance of Hole 24-233A. 3006 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 217 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 3712 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 267243 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 6 records from Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ‘ Piton de la Fournaise’, in Réunion Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae). 408 records from Birds Specimens of Akita Prefectural Museum. 5 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 5 records from Certain species of Plecoptera from the headwater springs of National Integration River (São Francisco), Brazil. 3 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 2 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 26841 records from MSUM Ichthyology and Herpetology Collections. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 371 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 25 records from Two new species of the gobiid fish Trimma from the coral reefs of the western Pacific Ocean (Pisces; Perciformes; Gobioidei).. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 8 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 7 records from A new species of Dwarf Japalura sensu lato (Reptilia: Squamata: Agamidae) from the upper Mekong River in Eastern Tibet, China, with notes on morphological variation, distribution, and conservation of two congeners along the same river. 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 184807 records from Tiroler Landesmuseum Ferdinandeum. 89 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 9 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 68 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 1192 records from Pollen profile from a swamp at Seelohe, Fichtelgebirge, Germany. 78 records from Mammals (GNHM-MM). 12 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 1 records from Bryozoans Specimens of Akita Prefectural Museum. 173 records from Fundación Miguel Lillo - Colección Invertebrados. 22 records from South American Antarctic Marine Biodiversity Literature. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 3 records from F. L. de Castelnau’s Norman River fishes housed in the Macleay Museum, University of Sydney. 1 records from One new species of Amphinemura and description of the female of A. ancistroidea Li & Yang (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China. 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 22 records from Thirteen new records of ferns from Brazil. 8 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 351 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 679 records from Collection Hydrozoa - ZSM München. 2 records from Redescription of the Amazonian tiny tree toad Amazophrynella minuta (Melin, 1941) (Anura: Bufonidae) from its type locality. 202386 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 10 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 2 records from A new species of Tyrannoseira (Collembola: Entomobryidae: Seirini) from the Brazilian coastal region. 34 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 4792 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 3 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 34 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 15 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 71 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 725 records from Relative abundance of Neogene nannofossils at ODP Site 165-998 from the Caribbean. 1872 records from Herbier National de Guinée (HNG) (BID-AF2015-0066-REG). 39 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 651 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 6071 records from EDIT - ATBI in Gemer area (Slovakia). 14 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 78 records from Nannofossil abundance of Hole 27-259. 7 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 2 records from AKG-Gelände (Bensheim). 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 5 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 4926 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 6 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 16128 records from Colección Ictiológica del Instituto Alexander von Humboldt. 159 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 4546 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 33 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 6 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 1 records from Lebensraum Gesamtschule (Langerwehe). 425 records from Foraminifera abundance of Hole 64-481. 2905 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-9. 15754 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 1350 records from ENBI WP 13 Martius C. F. P. von Collection subset (Muenchen). 2568 records from Fish (NHMK-PI). 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 174 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 106 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 34 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 844 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 2 records from Phylogeny of Bathysciotina Guéorguiev, 1974, based on morphology with a special emphasis to Italian genera and with the description of a new species of Halbherria (Coleoptera Leiodidae Cholevinae Leptodirini). 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 68 records from Nannofossil abundance of Hole 73-521A. 19 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 2 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 6 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 345 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 19 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 5 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 7887 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 750 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 15 records from Conringia orientalis. 12147 records from Danish Ants (Formicidae). 25 records from Brown algae specimens of Komatsu City Museum. 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 25098 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 207 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 370 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 2043 records from The Broward College Insect Collection. 24283 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 11 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 30 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 139383 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 2 records from On the identity of the genus Flavoperla (Plecoptera: Perlidae), with description of a new species in southwestern China. 17 records from Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico. 2 records from The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini). 5 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 2 records from A new slipper lobster of the genus Petrarctus Holthuis, 2002 (Crustacea, Decapoda, Scyllaridae) from Southwest coast of India. 4 records from New species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Brazil and Suriname. 155 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 12 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 149 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 2364 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 83 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 3 records from Results of palynological analysis of Hole 302-M0004C. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 794914 records from Western Australian Museum provider for OZCAM. 6 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 3998 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 1 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 424 records from Mamíferos voladores y no voladores del suroccidente colombiano. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 749 records from (Appendix Table 3) Relative abundances of planktonic foraminiferal species in sediment core MD01-2390. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from A new high-altitude species of centipede from the Andes of Ecuador (Chilopoda, Geophilomorpha, Schendylidae). 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1513 records from M. Gollop Collection. 37 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 53204 records from Naturalis Biodiversity Center (NL) - Diptera. 2 records from Schulhof Gymnasium Hürth Bonnstrasse. 1 records from Berlese's Primitive Oribatid Mites. 203 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 12 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 6357 records from Distribution of foraminifera of sediment core GIK23258-2. 307 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 6 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 62 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 97 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 47548 records from University of Minnesota Insect Collection. 16 records from Insect Collections of Okomu National Park- Nigeria. 235 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 19 records from Heinersdorfer Sumpfwiese. 291402 records from ARABEL - Arachnologia Belgica. 9 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 95 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 1 records from A new species of the genus Megophrys (Anura: Megophryidae) from Yunnan Province, China. 348 records from Antarctic pycnogonids. 62776 records from MLZ Bird Collection (Arctos). 26 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 14 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 3 records from Redescription of Honduriella maxima Denmark & Evans (Acari: Mesostigmata: Phytoseiidae), description of a new species of Honduriella Denmark & Evans from the Amazonian Forest, and a modified characterisation of the genus. 39 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 1 records from Naturschutzgebiet Müchelholz (Mücheln). 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 3 records from Wiese am Waldrand (Gurtweil). 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 6 records from Two new species of Nemouridae (Plecoptera) from Vietnam. 351 records from UWYMV Herpetology Collection (Arctos). 104386 records from Herbarium Senckenbergianum (FR) - Fungi. 2000 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 8 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 386 records from (Table 3) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704A. 320 records from Myxomycetes collection of the University of Eastern Finland. 47 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 70 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 19 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 14009 records from Collection Trichoptera - SMF. 2 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 21 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 235 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 107285 records from Arizona State University Hasbrouck Insect Collection. 21 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 429 records from Collection Strepsiptera SMF. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 3587 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 240 records from Chironomid remains in the sediment sequence of Site PG1212. 5316 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 3383 records from Lista florística de la Costa Grande del estado de Guerrero. 12 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 351 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 2 records from Amtsrain Apolda-Zottelstedt. 66116 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 36 records from A revision of the genus Medmassa Simon, 1887 (Araneae: Corinnidae) in the Afrotropical Region. 83 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 18 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 15 records from Redescription of the Indo-West Pacific scorpionfish Scorpaena neglecta Temminck & Schlegel, 1843, a senior synonym of four nominal species (Teleostei: Scorpaenidae). 79 records from Catalogue of the Syrphidae of Egypt (Diptera). 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 187 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 2 records from Dorfrand Mauderode. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 2 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica). 10 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 18224 records from K-State Museum of Entomological and Prairie Arthropod Research. 5 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 2274 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 1 records from Discovery of a new species of Dryocosmus Giraud, 1859 (Hymenoptera: Cynipidae: Cynipini) on Castanopsis tibetana from China. 80 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 13 records from An annotated species list of regular echinoids from Sri Lanka with notes on some rarely seen temnopleurids. 29876 records from European Moth Nights. 1127 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 24795 records from Université d'Aix-Marseille. 2068 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 4 records from MfN - Micropaleontology. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 296 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 12 records from BUND - Dassower See (Lübeck/Dassow). 25 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 36 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 23 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 356 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 1 records from Cuxhavener Küstenheiden. 5 records from Two new species of genus Lasiosina Becker from China (Diptera, Chloropidae). 2401 records from UWYMV Bird Collection (Arctos). 11994 records from Hatikka Observation Database. 200187 records from inatura - Erlebnis Naturschau Dornbirn. 19 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 3 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 2020 records from Birds (NHMK-BI). 7 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 11 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 6 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 134 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 4 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 11584 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 1 records from Description of a new species of Acrostichus Rahm 1928 (Nematoda: Diplogastridae) from India with a note on its position and relationship with the congeners. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 1275 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 107580 records from Database of invertebrates collected in Mongolia. 26 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 10075 records from Nematoda of Costa Rica (INBio). 32916 records from Insect specimen database of Atsugi City Museum. 75 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 177 records from Nannofossil abundance of Hole 30-285A. 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 607 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 213 records from Pollen record of profile 3TZ. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 373028 records from South Australian Museum Australia provider for OZCAM. 25 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 3 records from A new species of forest-dwelling Cyrtodactylus Gray (Squamata: Gekkonidae) from the Indawgyi Wildlife Sanctuary, Kachin State, Myanmar. 100 records from Brock University Herbarium (BU). 148 records from Herbarium BSG Hepaticopsida. 214 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1246-4. 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 309 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 5 records from A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini). 38 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 86 records from UWIZM Cnidarians. 17 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 119 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 1059 records from irregularia_mexico. 280 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 152102 records from Tasmanian Museum and Art Gallery provider for OZCAM. 40177 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 968 records from TTRS Mammals. 9 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 15 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 35 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 887 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 3627 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 95 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2 records from Mormolyce matejmiciaki sp. nov. (Coleoptera: Carabidae: Lebiinae) from Borneo. 99749 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 2799 records from University of Sindh Jamshoro Herbarium. 6 records from New Galumnoidea (Acari, Oribatida) from Hanoi (Northern Vietnam). 1140 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 76 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 5 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 3 records from A new subfamily, Styracurinae, and new genus, Styracura, for Himantura schmardae (Werner, 1904) and Himantura pacifica (Beebe & Tee-Van, 1941) (Chondrichthyes: Myliobatiformes). 50 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 159 records from Nannofossil abundance of Hole 67-499B. 3933 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 11 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 7873 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 19 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 2 records from Naturgrundstück (Eutin). 12127 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 28 records from Korean Plant Virus Database. 36 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 381 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 29 records from Herbarium Senckenbergianum (FR) - Protista. 3 records from Zoology in the Middle East. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 25 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 159 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 1354 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 39 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 189 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 5448 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 204 records from Echinoderms from the Seaflower Biosphere Reserve. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 73 records from (Appendix A) Sea surface temperture reconstruction for ODP Hole 117-723A. 218 records from Nannofossil abundance of Hole 49-408. 25 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 282877 records from Allan Herbarium (CHR). 254268 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from Pinguisoperla, a new fossil genus of Perlidae (Insecta: Plecoptera) from mid-Cretaceous Burmese amber. 4 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 14275 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 27 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 3 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 265 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1244-2. 5 records from Cladocera from the Upper Xingu River Basin with the description of a new genus of the Chydoridae (Crustacea: Branchiopoda: Anomopoda). 4 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 5428 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 2 records from Warnowtal (Rostock). 62 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 27830 records from Marie-Victorin Herbarium (MT) - Bryophytes. 330 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 3 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 181 records from Dinoflagellate cysts from sediment core PS1295-4. 9 records from The genus Jeekelosoma Mauriès, 1985 - Moroccan cave millipedes (Diplopoda, Polydesmida, Paradoxosomatidae). 177 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 83 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 186 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 4 records from The identity of Osteobrama cotio, and the status of “ Osteobrama serrata ” (Teleostei: Cyprinidae: Cyprininae). 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 3190 records from Utah State University, Intermountain Herbarium. 946 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 978 records from Sammlung Eggers Westindien Herbarium Hamburgense HBG. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 9902 records from DSMZ Bacteria. 247807 records from CAS Entomology (ENT). 39614 records from Naturalis Biodiversity Center (NL) - Pisces. 32 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 74 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 9000 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 871 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 221 records from Revision of the genus Dziriblatta Chopard, 1936 (Blattodea, Ectobiidae, Ectobiinae) from North Africa, Spain, and the Macaronesian islands. I. The nine subgenera of the genus. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 19 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 1351 records from (Appendix B) Relative abundances of larger size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 10212 records from Spider (NSMK-SP). 26791 records from OUPR - Herbário "Professor José Badini". 15 records from Nannofossil abundance of Hole 58-442B. 64 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 101 records from Mammals of Korea: a review of their taxonomy, distribution and conservation status. 433 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 4 records from VFD-H: Heidenrod: Pferdeweide Mürth. 10650 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 42 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 1 records from Resurrection of the earthworm species Dendrobaena fedtschenkoi (Michaelsen, 1900), a former synonym of Dendrobaena byblica (Rosa, 1893) (Clitellata: Megadrili). 104 records from Range table from benthic foraminifers in ODP Hole 172-1059B. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 18 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 6 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 2 records from A new species of Yllenus Simon, 1868 from northern India (Araneae, Salticidae). 1 records from Nottekanal, Klasse 7 - 10. 311 records from Nannofossil abundance of Hole 37-333. 5923 records from Australian Coral Ecoregions. 1 records from A new species of Ohilimia Strand, 1911 from New Guinea (Araneae: Salticidae). 12 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 11 records from The identity of the Carsidara species (Hemiptera: Psylloidea: Carsidaridae) associated with Firmiana simplex (Malvaceae) in Japan and Korea. 2007 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 9 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 4221 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 897332 records from MICROBIS database. 9 records from The bark louse family Stenopsocidae (Psocodea: Psocomorpha) newly recorded from Laos, with description of three new species. 5 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 146 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 604 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 5710 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 36 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 37 records from Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia.. 293 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 2 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 43770 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 134 records from Pollen profile II/B at Krumbach, Germany. 36162 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 22 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 36 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 3 records from Nationalpark Harz Schul-AG Braunlage. 600 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 5 records from A new species of Pyrrhosphodrus (Hemiptera: Heteroptera: Reduviidae) from the Caatinga ecosystem in Brazil, with notes on the genus. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 77 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 440 records from Wichita State University Collection. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 647 records from pbzt_insect_biodiversity. 7 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 281 records from NZCS Upper Tapanahony Expedition 1991. 1 records from Oppia nitens. 24 records from Tanzanian Vertebrate Collection. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 603 records from Fossil (NSMK-FO). 2 records from First Jurassic grasshopper (Insecta, Caelifera) from China. 57928 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 7 records from Philippogalla, a new genus for Philipposcopus modestus (Baker) from the Philippines, and a new species of Philipposcopus (Hemiptera: Cicadellidae: Idiocerinae) from China. 6 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 128 records from Coleção de Nematoda do Museu Nacional - UFRJ. 8 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 9 records from One new species of the genus Acosmetura and supplement of Acosmetura emeica Liu & Zhou, 2007 (Tettigoniidae: Meconematinae) from Sichuan, China. 22 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 1 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 4728 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 7 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 11249 records from Heteroptera collections of SW Finland. 2740 records from Fungi specimens of Saitama Museum of Natural History. 1543 records from Pollen record of sediment core Bokanjacko Blato 1. 1129 records from Mollusca Collection of Saitama Museum of Natural History. 31 records from Three new species of Diduga Moore, [1887] (Lepidoptera, Erebidae, Arctiinae) from Cambodia. 1 records from Oribates fusifer. 24 records from Paracobitis abrishamchiani, a new crested loach from the southern Caspian Sea basin (Teleostei: Nemacheilidae). 4 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 4 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 602 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 2 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 75 records from Nemertini - SMF. 5 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 46680 records from Bosque Mesófilo de Montaña de México. 57 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 3 records from A new species of frog (genus Eleutherodactylus) from a cloud forest in Western Colombia. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 1004 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 120410 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 5410 records from Collection ornithologique A. Maës. 31 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 2 records from New Entodiniomorphid Ciliates, Buetschlia minuta n. sp., B. cirrata n. sp., Charonina elephanti n. sp., from Asian Elephants of Turkey. 5 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 89 records from Mammal specimens of Komatsu City Museum. 1 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 3 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 1490 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 27578 records from Natural History Museum Rotterdam (NL) - Chordata collection. 12 records from Mamíferos del municipio de Santa Bárbara, Santander - Proyecto Santander BIO. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 37 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 406575 records from Herbarium of Taiwan Forestry Research Institute. 3698 records from NIWA Invertebrate Type Collection. 5 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 7066 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 258 records from Malawi-Histeridae-Biodiversity-Data. 1 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 16 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 41 records from Registros Primates Neotropicales Convocatoria APC. 19 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 4 records from Cribrilinids (Bryozoa, Cheilostomata) associated with deep-water coral habitats at the Great Bahama Bank slope (NW Atlantic), with description of new taxa. 134 records from Pollen record of profile 3TZ2. 1 records from Hoplophora ardua. 43 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna”. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 14 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 7128 records from La familia Asclepiadaceae en México. 18 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 17 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 34 records from Morphological examination and phylogenetic analysis clarify the taxonomic status of Cuban Longior Travassos & Kloss, 1958 (Nematoda: Thelastomatoidea: Hystrignathidae). 54 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 54 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 4 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 30004 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1 records from Abcoronalis protrusus, a new paraboloponine genus and species (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Borneo. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 50 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 1 records from A new record of Potamanthellus caenoides Ulmer 1939 (Ephemeroptera: Neoephemereidae) from the southern Western Ghats of India. 8462 records from University Of Pretoria: Lacewing Database Project (1911-2015). 383 records from Nannofossil abundance of Hole 66-490. 4400 records from USAC Mammals Collection. 20 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 218 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 3399 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 363 records from PSUZC-Reptile Collection. 82 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 1136 records from Nannofossil abundance of Hole 82-558A. 1513 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 70 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 59 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 1 records from First columbellid species (Gastropoda: Buccinoidea) from deep-sea hydrothermal vents, discovered in Okinawa Trough, Japan. 569 records from (App 2) Relative contents of benthic foraminifera species in Holocene sediments from Core ASV11-858-3. 38 records from Visual Plants (144.41.33.158) - Plants from Costa Rica, illustrations by Teresa Barantes Lobo. 5640 records from Collection Echinodermata SMF. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 77414 records from MfN - Fossil vertebrates IV. 5020 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 46068 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 3439 records from MEXU/Flora de Oaxaca. 124 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 480 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 287 records from Nannofossil abundance of Hole 66-488. 5 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 2126 records from Dolichopodidae of Portugal - dataset 2009-2018. 1915 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 9304 records from Echinoderm collection of National Museum of Nature and Science. 109176 records from Herps Specimens. 54 records from Ompok platyrhynchus, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 30535 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 221 records from (Table 6) Ostracod assemblages of sediment core 9409. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 8 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 5 records from Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae). 498 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 4 records from Two new Afrotropical genera of Scatopsidae (Diptera). 3689 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 6 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 1153 records from Nannofossil abundance of Hole 17-167. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 4 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 5 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 1 records from Arthropoden aus südostalpinen Höhlen.. 289 records from bmhs_butterfly_collection. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 16 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 13945 records from MfN - Fossil plants (Paleophytic). 1139 records from SWECO. 1694 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 60887 records from EAC - Herbário Prisco Bezerra. 3 records from The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae). 30198 records from Collection Crustacea - ZMB. 726 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 18 records from Peckoltia cavatica, a new loricariid catfish from Guyana and a redescription of P. braueri (Eigenmann 1912) (Siluriformes).. 36 records from Nannofossil abundance of Hole 25-249. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 3 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 1399 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 154 records from Dermaptera in the icipe collection. 2344 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 33 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 73 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 11 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 16 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 1 records from Redescription of Parafronurus youi and generic affinities (Ephemeroptera, Heptageniidae, Ecdyonurinae). 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 12 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 23238 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 337 records from Pollen data of trap CB4. 15 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 11 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0004C. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 5 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 6859 records from Plan de vertebrados de la Patagonia. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 2 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 132 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 4 records from Danielsberg (Mölltal, Kärnten). 71 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 232661 records from Oklahoma Vascular Plants Database Provider. 350 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 740 records from Targeting a portion of central European spider diversity for permanent preservation. 48 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 10907 records from Census of species recorded during phytosociological surveys in Benin. 439 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 6579 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 6556 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 36 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 6 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 651 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 28396 records from Collection Pisces SMF. 4 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 7 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 8980 records from MEXU/Tipos de plantas vasculares. 56 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 1642 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 8 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 2 records from Landschaftspflegehof (Berlin). 1 records from Bachpatenschaft Beeke. 7 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 390 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 101 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 2 records from Artenvielfalt auf den Elbwiesen (Dessau). 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 194 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 2917 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 46933 records from Botanical Museum, Copenhagen, Mycology Herbarium. 17713 records from NCSM Mammals Collection. 100 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 1 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 76262 records from Colección de Entomología del Instituto Alexander von Humboldt. 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 57 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 1 records from On the Chilopoda from Turkey. 7 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 2 records from Planktic foraminifera counts of multinet PS2616-5. 4207 records from CASES2003_2004. 3 records from Nouvelles fourmis de Madagascar.. 376 records from Digitalización y sistematización de las colecciones biológicas del INECOL. 151 records from CHAS Botany Collection (Arctos). 32 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) - three possibly threatened Brazilian species. 20 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 47 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 836 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 3 records from Naturschutzgebiet Lochbusch-Königswiesen. 13 records from Visual Plants (144.41.33.158) - Private collection of Florian Werner. 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 7814 records from Odonata de Veracruz. 621 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 3 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 15 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 3 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 6393 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 1379 records from Composition of the coccolith flora in sediment core GeoB1710-3. 11 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 127 records from Collection Ephemeroptera - SMF. 12 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 102476 records from Denver Museum of Nature & Science - Entomology. 42 records from (Table 1) Abundance, wet biomass, and carbon biomass of all major groups of phytoplankton in the water column of the Kara Sea. 34829 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 35 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 2 records from A second contender for “world’s smallest fly” (Diptera: Phoridae). 8 records from A taxonomic review of the genus Dicranorhina Shuckard (Hymenoptera: Crabronidae: Crabroninae) from the Indian subcontinent with the description of three new species from Southern Western Ghats. 8 records from American Asteraceae-feeding Astrotischeria species with a highly modified, three-lobed valva in the male genitalia (Lepidoptera, Tischeriidae). 5 records from Two new orthoclad species from Colombian Andes (Diptera: Chironomidae). 2713 records from Relative abundances of planktonic foraminifera in ODP Site 121-758 (Table 1). 422 records from Collembola of the Chernaya river basin. 16276 records from Coleoptera collection of Uunio Saalas. 1 records from Ueber Chilopoden aus westbalkanischen Hoehlen. 1070 records from CNAN/Araneae. 28 records from Anfibios y reptiles de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 18047 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 585 records from Checklist and taxonomic changes for Central and South American Philonthina (Coleoptera: Staphylinidae). 8 records from Validation of the names of eight species of Blattaria according to the Rules of Zoological Nomenclature. 6 records from Anurogryllus Saussure, 1877 (Orthoptera: Gryllidae: Gryllinae) from southern Brazil: new species and new records. 79 records from Foraminifera abundance of sediment core C1960.201. 1 records from Channa pseudomarulius, a valid species of snakehead from the Western Ghats region of peninsular India (Teleostei: Channidae), with comments on Ophicephalus grandinosus, O. theophrasti and O. leucopunctatus. 1 records from The millipede Typhloglomeris caucasica Golovatch, 1975 found epigeically (Diplopoda, Glomerida, Glomeridellidae). 28 records from New records of lampriform fishes (Teleostei: Lampriformes) from the Pacific coast of lower Central America, with comments on the diversity, taxonomy and distribution of the Lampriformes in the eastern Pacific Ocean. 3979 records from Colección de Zoología Invertebrados - Helmintología. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 13204 records from Algunas especies de anfibios y reptiles contenidos en el Proyecto de Norma Oficial Mexicana PROY-NOM-059-ECOL-2000. 7170 records from The Bergius Herbarium. 190322 records from Terrestrial and liminic invertebrates systematic collection NTNU University Museum. 362 records from Museo Argentino de Ciencias Naturales (MACN), Buenos Aires: sea stars collection (Asteroidea, Echinodermata). 6 records from Three new species of Claudiella Reichardt & Vanin, 1976 (Coleoptera, Torridincolidae) from Brazil. 101 records from Revision of the genus Acylophorus Nordmann, 1837 from Madagascar and Mascarene Islands (Coleoptera: Staphylinidae: Staphylininae: Acylophorina). 21 records from The Resin and Carder bees of south India (Hymenoptera: Megachilidae: Anthidiini). 1 records from Laimosemion leticia (Teleostei: Cyprinodontiformes: Rivulidae), a new species from the upper Rio Amazonas, Southern Colombia. 2 records from Systematics of Guajirolus ektrapeloglossa Flowers 1985 (Ephemeroptera: Baetidae). 228 records from MNA (Section of Genoa) and NIWA Invertebrate Collection - Ross Sea Tanaidacea. 173 records from Review of the mirine plant bug genus Eurystylus Stål from Japan and Taiwan (Hemiptera: Heteroptera: Miridae: Mirinae), with descriptions of two new species, a new synonymy and a new combination. 3 records from Contribution to the knowledge of the genus Visiana Swinhoe (Lepidoptera: Geometridae: Larentiinae), with the description of two new species from Indonesia. 62 records from Genotipificación de especies de la ictiofauna del Sistema Pánuco-Tamesí a través de la generación del código de barras de ADN mitocondrial. 18900 records from UCBG TAPIR Provider. 167 records from Morfología funcional de mantos de rodolitos en el golfo de California, México. 133 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/042-2. 65 records from ZUEC-CNI - Coleção de Cnidaria do Museu de Zoologia da UNICAMP. 6255 records from Banco de datos de la ictiofauna del Río Bravo desde 1902 a 1992 en la colección ictiológica de la UANL. 3487 records from MUFAL herbarium - Museu de História Natural da Universidade Federal de Alagoas - Herbário Virtual REFLORA. 5 records from renaturierter Main (Kemmern bei Bamberg). 70 records from Contribución a la distribución, ecología y estado de conservación de dos especies del género Sceloporus, endémicas de la región del Cabo, Baja California Sur. 13469 records from Montana State University - Billings. 447 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 665 records from Geochemistry and sedimentology on core POS200/10_28-1. 3 records from Palaeopsylla (Palaeopsylla) aysenurae n. sp., a new ctenophthalmid flea (Siphonaptera: Ctenophthalmidae) from Turkey. 1 records from Description of a new branchiate scale-worm (Polychaeta: Polynoidae) from the hydrothermal vent on Southwest Indian Ocean Ridge. 244573 records from Oskarshamn herbarium (OHN). 347 records from Distribución de peces dulceacuícolas introducidos en las cuencas del México central, con especial atención a las localidades dentro del área de distribución de los peces endémicos de la familia Goodeidae. 6 records from A new species of salamander of the genus Hynobius (Amphibia, Caudata, Hynobiidae) from South Korea. 8 records from Records of Wenchengia (Lamiaceae) from Vietnam. 1219 records from Ortopteroides de Oaxaca, México: Orthoptera, Mantodea y Phasmatodea. 195 records from Plant macrofossil concentrations from an open section of Lac de Fully sediments. 10 records from Lectotype designations, taxonomic notes and new synonymy in some species of the bee genus Centris Fabricius, 1804 described by William Henry Fox (Hymenoptera: Apidae). 173 records from Anfibios y reptiles del municipio de Cimitarra, Santander - Proyecto Santander BIO. 1 records from A New Genus and Species of Clingfish (Teleostei: Gobiesocidae) from Western Australia. 3273 records from Algae collection. 95 records from Riqueza específica, distribución y abundancia de aves terrestres y marinas en Isla San José, Golfo de California, Baja California Sur, México. 311 records from Names of hydroids (Cnidaria, Hydrozoa) established by Charles McLean Fraser (1872 - 1946), excluding those from Allan Hancock Expeditions. 2 records from A new species of Phyllodytes Wagler, 1830 (Anura, Hylidae) from the Atlantic Forest of southern Bahia, Brazil. 6 records from Taxonomic contribution to the genus Sphaerosyllis (Annelida: Syllidae: Exogoninae) in the Black Sea. 9269 records from Relative abundance of benthic foraminifera in sediment core M5/2_KL15. 15 records from A key to the East Palaearctic and Oriental species of the genus Rhysipolis Foerster, and the first host records of Rhysipolis longicaudatus Belokobylskij (Hymenoptera: Braconidae: Rhysipolinae). 5 records from Immature stages of the Australian flower-loving fly Apiocera striativentris (Diptera: Apioceridae). 31 records from The identity of catfishes identified as Mystus cavasius (Hamilton, 1822) (Teleostei: Bagridae), with a description of a new species from Myanmar.. 26319 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 968 records from Guinea-Bissau Herpetological Collection - IICT. 84 records from Synopsis of the bee genus Thygater Holmberg 1884 (Hymenoptera, Apidae) in the Brazilian state of Minas Gerais, with the description of a new species and a key to all Brazilian species. 908 records from Códigos de barras del ADN de mamíferos topotipos de México Fase I: Noroeste mexicano. 3 records from A new species of Schindler's fish (Teleostei: Gobiidae: Schindleria) from the Malay Archipelago (Southeast Asia), with notes on the caudal fin complex of Schindleria. 41 records from Species of Ancistrus (Siluriformes, Loricariidae) from Ecuador, with the description of a new species from the Amazon River Basin. 517 records from Crustáceos macrobénticos de la plataforma y talud continental del Golfo de México. 1 records from Validation of Tethya samaaii Ribeiro & Muricy, 2011, replacement name for the sponge Tethya rubra Samaai & Gibbons, 2005 (Demospongiae, Tethyida, Tethyidae). 8 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 1 records from On the Chilopoda from Turkey. 42 records from A review of the Barsine obsoleta species-group with description of a new species from Vietnam (Lepidoptera, Erebidae, Arctiinae). 107 records from The Stephanidae (Hymenoptera) of Mexico, with description of six new species and key to western Foenatopus Smith. 1 records from A new garden eel, Heteroconger fugax (Congridae: Heterocongrinae), from the northwestern Pacific Ocean. 16 records from Contributions to the millipede genus Nepalella Shear, 1979 from China, with four new species and first results on phylogeny based on DNA-barcoding (Diplopoda, Chordeumatida, Megalotylidae). 21 records from Revision of the Palaearctic and Oriental species of the genus Oides Weber, 1801 (Coleoptera: Chrysomelidae: Galerucinae). 7 records from The pliomerid trilobite Ibexaspis and related new genera, with species from the Early Ordovician (Floian; Tulean, Blackhillsian) of the Great Basin, western USA. 56 records from Shallow-water Demospongiae (Porifera) from Sodwana Bay, iSimangaliso Wetland Park, South Africa. 1 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 25 records from Four new and one newly recorded species of Diduga Moore, [1887] (Lepidoptera, Erebidae, Arctiinae) from Vietnam, with redescription of the little known species Diduga haematomiformis van Eecke, 1920. 7 records from of patch-nosed snake (Colubridae: Salvadora Baird and Girard, 1853) from Oaxaca, Mexico. 3 records from Redescription of Lernaeenicus stromatei Gnanamuthu, 1953 (Copepoda: Siphonostomatoida: Pennellidae) infesting the Black Pomfret Parastromateus niger (Bloch) from Indian waters. 1458 records from HUCPE - Herbário da Universidade Católica de Pernambuco. 135 records from VMNH SVDM Invertebrate Paleontology. 756 records from Range table from benthic foraminifers in ODP Hole 139-857A. 3397 records from Occurrences portant sur 941 espèces de plantes appartenant à 45 familles de l'herbier du Centre National de Floristique, en Côte d'Ivoire. 148 records from (Table 4) Dinoflagellate cysts from sediment core PS1295-5. 357 records from POPA- Fisheries Observer Program of the Azores: Sea bird sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 15 records from A new species of the genus Protopolybia Ducke, 1905 (Hymenoptera, Vespidae, Polistinae), with taxonomic contributions to the exigua species-group. 274 records from Taxonomic revision of Agraphydrus Régimbart, 1903 I. China and Taiwan (Coleoptera: Hydrophilidae: Acidocerinae). 10 records from The Pselaphinae (Coleoptera: Staphylinidae) of Madagascar. VI. Description of Ambohitantella banari gen. et sp. n. with notes on Nearticerodes Jeannel, 1954 and Triceratomerus Jeannel, 1960. 66 records from Four new species and further contributions to the Leuctridae (Plecoptera) of the Korean Peninsula. 6627 records from ATCC Fungi Collection Catalog. 2 records from New Cheilostomata (Bryozoa) species from sublittoral and bathyal zones off the Faroe Islands, with some comments on allied taxa. 44 records from New records of chalcidid (Hymenoptera: Chalcididae) pupal parasitoids from India. 18 records from Taxonomic studies on the genus Orancistrocerus van der Vecht, 1963 (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 25 records from Glyptothorax botius (Hamilton, 1822), a valid species of catfish (Teleostei: Sisoridae) from northeast India, with notes on the identity of G. telchitta (Hamilton, 1822).. 183 records from BID-Malawi's-Notodontidae-Biodiversity-Data. 2034 records from Coleoptera Collection. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 1 records from Nothrus peltifer. 232 records from North Marine Region sawfish collection records (DEW collation), Australia (1912 - 2004). 371 records from Planktic foraminifera and paleoclimate temperature and salinity calculations from sediment core M44/1 GeoTü KL71. 2 records from A unique new genus and species of the phyline plant bug tribe Hallodapini from the Philippines and Thailand (Hemiptera: Heteroptera: Miridae: Phylinae: Hallodapini). 3064 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hymenoptera (ZUFMS-HYM). 75 records from Annotated list of Mimallonidae (Lepidoptera, Mimallonoidea) from Trinidad and Tobago, with the description of a new species of Cicinnus Blanchard, 1852 and taxonomic notes. 27585 records from The Fungal, Lichen and Plant Collections at the Herbarium Marburgense. 177 records from Manual para la identificación de lianas en el campo. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 140 records from An annotated catalogue of Elachistinae of the World (Lepidoptera: Gelechioidea: Elachistidae). 7 records from Taxonomic revision of the microleafhopper genus Limassolla Dlabola from Korea (Hemiptrea: Cicadellidae: Typhlocybinae). 1 records from Lauchhamer GEO-Tag der Artenvielfalt. 1 records from Nouvelles fourmis d'Afrique.. 25 records from First Australian records of Ethusina (Crustacea: Decapoda: Ethusidae) and additional records from New Zealand. 43 records from Miscophus Jurine, 1807 (Hymenoptera, Crabronidae) in Central, Northern, and Eastern Europe. 1 records from Revisiting Gryposuchus jessei Gürich, 1912 (Crocodylia: Gavialoidea): specimen description and comments on the genus. 1200 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 30 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 6 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 6 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 4439 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 25374 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 1078 records from Pollen profile from Seminary School Basin. 1 records from Schistura alboguttata, a new loach species of the family Nemacheilidae (Pisces: Cypriniformes) from the Pearl River basin in Guangxi, South China. 3 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 12 records from Rotundocoris, a new apterous genus of Carventinae from China (Heteroptera: Aradidae). 3304 records from Benthos counted on dredged samples during Valdivia cruise VA53. 1 records from Oribates calcaratus. 96 records from The species of the genus Diaclina Jacquelin du Val (Coleoptera: Tenebrionidae: Alphitobiini) from Sub-Saharan Africa. 115 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 487257 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1000 records from Axel W. Erikssons African Bird Collection at Vänersborg Museum. 5335 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 1882 records from Carabidae of the European North-East of Russia. 4019 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 1057 records from Palynological analysis of sediment core GeoB9508-5. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 9997 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 35 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 52 records from Pelvicachromis signatus and Pelvicachromis rubrolabiatus, two new cichlid species (Teleostei, Perciformes) from Guinea, West Africa.. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 29137 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 41 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 593 records from Flux data of NU2_trap (Table A1). 228 records from Bishop's University Insect Collection (BUIC). 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 16 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 47 records from Chameleonfishes in Bangladesh: hipshot taxonomy, sibling species, elusive species, and limits of species delimitation (Teleostei: Badidae). 134104 records from BioFokus. 6 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 71494 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 1824 records from CNAN/Scorpiones. 104 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 8649 records from Fossil (WSHN-FO). 4 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 4 records from Two new genera and species of the leafhopper tribe Idiocerini (Hemiptera: Cicadellidae) and redescription of the type species of Paraidioscopus. 7 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 7 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 7 records from Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species. 13 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 8 records from A new species of Orthosiphon (Lamiaceae) from Angola. 425 records from Collection de C.C.H. Jongkind aux Monts Nimba (BID-AF2015-0066-REG). 281 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 2443 records from Cnidaria MZS. 5 records from A new Brazilian species of Harpasus Mulsant (Coleoptera, Coccinellidae, Chilocorinae), a predator of Tinocallis kahawaluokalani (Kirkaldy) (Hemiptera, Aphididae). 26 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 4 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 7351 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 13 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 14 records from Laetosphecia, a new genus of clearwing moths from south-eastern China, with a brief review of the Sesiini from China (Lepidoptera, Sesiidae). 8 records from A review of the ant genus Metapone Forel from Madagascar.. 907 records from Pollen profile Märchenwald B, Harz, Germany. 6 records from Mammalia (JNHM-MM). 115 records from On the absence of the Green-tailed Trainbearer Lesbia nuna (Trochilidae) from Venezuela: an analysis based on environmental niche modelling. 10 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 13940 records from The Vascular Plants Collection of the University of Goettingen. 2120 records from Flora vascular acuática de la cuenca del Río Tamesí. 59 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 54 records from The bee Ruizanthedella mutabilis Spinola (Hymenoptera: Halictidae): a very common but poorly known species studied using integrative taxonomy. 13 records from A new genus and two new species of miniature clingfishes from temperate southern Australia (Teleostei, Gobiesocidae). 5664 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 5 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 732 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 9 records from New data on brown lacewing genus Wesmaelius Krüger, 1922 from China (Neuroptera, Hemerobiidae), with a key to Chinese species. 5327 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 10509 records from Andes to Amazon Biodiversity Program. 182790 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 665 records from Collection Echinodermata - ZMB. 28 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 1 records from WildesMoor bei Schwabstedt. 443 records from Inventario herpetofaunístico del noroeste de Hidalgo. 391 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 3559 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 3 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 12 records from Update of the genus Leptochiton (Mollusca: Polyplacophora) in Chilean deep waters: three new reports and description of two new species. 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 234 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 8 records from A taxonomic review of the genus Triscaedecia (Lepidoptera: Alucitidae) in the world fauna. 13 records from Aves de fragmentos de Bosque seco en la región del Caribe Colombiano. 4 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 11 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 2326 records from Jardín Botánico Atlántico, Gijón: JBAG. 1 records from Description of a new species of the Ponerine ant genus, Emeyopone (Hymenoptera: Formicidae) from Karnataka, India.. 1137 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 1 records from A new species of Rock Gecko of the genus Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from Belitung Island, Indonesia. 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 7 records from Three new species of Epigomphus (Odonata: Gomphidae) from Costa Rica. 2340 records from Type Specimen Database of Museum and Institute of Zoology PAS. 3784 records from Herbier de Wallis et Futuna. 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 17 records from Two amazing new species of treehoppers (Hemiptera: Membracidae) from Colombia: Calloconophora estellae sp. nov. and Problematode robertoi sp. nov.. 9 records from New species of Tenebrionidae Latreille, 1802 (Coleoptera: Tenebrionoidea) from the Philippines. 2 records from A new flower fly species of Cepa Thompson & Vockeroth (Diptera: Syrphidae) from the Valdivian evergreen forest hotspot, Chile. 9 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 416 records from Data collected during the expeditions of the e-learning projects Expedition Zeeleeuw and Planet Ocean. 55 records from Highland biodiversity of Fanniidae (Insecta, Diptera): fourteen new species from the Andes and Central America. 301353 records from University of Florida Invertebrate Paleontology. 6 records from Alburnus magnificus, a new species of bleak from the Orontes River drainage (Teleostei: Leuciscidae). 8 records from Endangered beauties: micro-CT cranial osteology, molecular genetics and external morphology reveal three new species of chameleons in the Calumma boettgeri complex (Squamata: Chamaeleonidae). 695 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 94-608 in the North Atlantic. 3 records from The spider genus Hersilia in Thailand, with descriptions of two new species (Araneae, Hersiliidae). 2 records from Anagrus turpanicus sp. n. (Hymenoptera: Mymaridae) from China, an egg parasitoid of Arboridia kakogowana (Hemiptera: Cicadellidae). 1 records from Physoschistura walongensis, a new species of loach (Teleostei: Nemacheilidae) from Arunachal Pradesh, northeastern India. 7 records from Three new species of the genus Mimetus Hentz, 1832 (Araneae: Mimetidae) from Yunnan-Guizhou Plateau of China. 7 records from Five new species in the genus Leschenaultia Robineau-Desvoidy, 1830 (Diptera: Tachinidae) from Mato Grosso, Mato Grosso do Sul and Rondônia, Brazil. 35 records from Range table from planktonic foraminifers in ODP Hole 139-857B. 9 records from Six freshwater microturbellarian species (Platyhelminthes) in permanent wetlands of the Coastal Plain of southern Brazil: new records, abundance, and distribution. 37675 records from UAM Bird Collection (Arctos). 2 records from Description of Metarhabditis giennensis sp. n. (Nematoda, Rhabditida, Rhabditidae) from decaying wood of a riverbank forest in the southern Iberian Peninsula. 16 records from A new species of chimaeroid, Hydrolagus alphus sp. nov. (Chimaeriformes: Chimaeridae) from the Galapagos Islands.. 6 records from Two new species of Loboschiza from Cambodia and Vietnam (Lepidoptera: Tortricidae: Olethreutinae: Enarmoniini). 219 records from Revision of the Mesoamerican species of Calolydella Townsend (Diptera: Tachinidae) and description of twenty-three new species reared from caterpillars in Area de Conservación Guanacaste, northwestern Costa Rica. 1698 records from UTEP Herpetology Osteology (Arctos). 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 2 records from Revision of the tree crickets of China (Orthoptera: Gryllidae: Oecanthinae). 3 records from New Earwigs in Protodiplatyidae (Insecta: Dermaptera) from the Middle Jurassic Jiulongshan Formation of Northeastern China. 11 records from Tanytarsini (Diptera: Chironomidae) from madicolous habitat in Southeast Brazil: new species and new records. 13 records from Two new, brachypterous Limnellia species from the Venezuelan Andes (Diptera: Ephydridae). 41 records from Taxonomy of Tabanus trivittatus species-group (Diptera: Tabanidae), with description of five new species. 1 records from Acmaeodera (Ptychomus) kubani sp. n. from Northern Africa and the Arabian Peninsula, with notes on the taxonomic composition of the subgenus Ptychomus Marseul, 1866 (Coleoptera: Buprestidae: Polycestinae: Acmaeoderini). 2 records from Selz (Ingelheim am Rhein). 9 records from Four new species of Epacanthion Wieser, 1953 (Nematoda: Thoracostomopsidae) in intertidal sediments of the Nanji Islands from the East China Sea. 398 records from Tsetse flies of East Africa update. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 4 records from A new species of Heliothrips (Thysanoptera, Panchaetothripinae), based on morphological and molecular data. 2 records from Amphibia ZMK. 387 records from Distribución espacio-temporal de las larvas de atunes en el Golfo de Tehuantepec, México. 3 records from Redescription of Zoica puellula (Simon, 1898) (Araneae: Lycosidae: Zoicinae) and transfer of Zoica harduarae (Biswas & Roy, 2008) to Agelenidae C. L. Koch, 1837. 8 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 3 records from A new species of Notomulciber (Micromulciber) Aurivillius, 1913, from the southern Western Ghats of India (Coleoptera: Cerambycidae: Lamiinae: Homonoeini). 20755 records from pins. 1005 records from Collection Crustacea - KAUMM. 12 records from Revision of the genus Kailasha (Lepidoptera, Erebidae, Arctiinae) from Oriental region, with description of one new species. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 1 records from Two new species of Xyalidae (Monhysterida, Nematoda) from the East China Sea. 40 records from A review of the leafhopper genus Scaphoideus (Hemiptera: Cicadellidae: Deltocephalinae) from Guangxi of China, with description of one new species. 2177 records from SMNS Palaeontological collection - Invertebrates (Cenozoic). 2509 records from Colección de Oligoquetos Acuáticos de la UPV/EHU. 3 records from A new species of the genus Thrips (Thysanoptera: Thripidae) from the Western Ghats of India. 49 records from Mammal specimens of Natural History Museum, Kishiwada City. 381 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 12 records from Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean. 55683 records from UWBM Mammalogy Collection (Arctos). 4 records from A new species of Pselaphogenius Reitter, 1910 of the fiorii species group from southern Italy (Coleoptera, Staphylinidae, Pselaphinae). 2 records from Acromyrmex charruanus: a new inquiline social parasite species of leaf-cutting ants. 11129 records from Royal Ontario Museum Fungarium (TRTC). 486 records from El código de barras de las especies NOM-059 de mamíferos del Noroeste de México. 66 records from Notes on the shrimp genus Palaemon Weber, 1795 (Crustacea, Decapoda, Palaemonidae) and related genera from Taiwan. 23 records from Pachyrhynchus elenae Rukmane, 2016, a new synonym of Pachyrhynchus phaleratus Waterhouse, 1841 (Coleoptera: Curculionidae: Entiminae). 14052 records from Plant specimens of Horaiji-san Museum of Natural History. 19 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 6 records from Taxonomic status of the barbastelles (Chiroptera: Vespertilionidae: Barbastella) from the Japanese archipelago and Kunashir Island. 2 records from Düne am Ulvenberg (Darmstadt). 4 records from Ompok argestes, a new species of silurid catfish endemic to Sri Lanka (Teleostei: Siluridae). 1 records from A new species of Homatula from the Red River drainage in Yunnan based on morphological and genetic data (Teleostei: Nemacheilidae). 43857 records from Mammals housed at MHNG, Geneva. 12 records from Two new ‘ Asura - like’ Cyana Walker, 1854 from Africa (Lepidoptera, Erebidae, Arctiinae). 345 records from Phytoplankton abundance measured on water bottle samples at station PS65/424-3. 3 records from Grillhütte Wettsaasen, Wiese, Hecken. 2656 records from Swiss Psyllid (Hemiptera) Collections - Basel. 45 records from The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov.. 2 records from Spockia tagala gen. and sp. nov. a new monotypic genus of Asopinae (Hemiptera: Heteroptera: Pentatomidae) from the Philippines. 2 records from New species of Trichomycterus (Siluriformes: Trichomycteridae) lacking pelvic fins from Paranapanema basin, southeastern Brazil. 225 records from UWIZM Mantodea. 5 records from A new and five rare bdelloids from Korea. 536 records from Distribución actual y potencial de veinte especies de hongos silvestres comestibles en los bosques de coníferas del estado de Oaxaca. 10 records from Validation of the status of a species with high CO 1 and low nuclear genetic divergences: the scab mite Caparinia ictonyctis stat. res. (Acariformes: Psoroptidae) parasitizing the African hedgehog Atelerix albiventris. 7 records from Review of the Oriental leafhopper genus Parafagocyba Kuoh & Hu (Hemiptera: Cicadellidae: Typhlocybinae: Typhlocybini), with descriptions of three new species from China. 659 records from Taxonomía y prospección del hábitat de las poblaciones de Bursera sect. Bullockia con especial énfasis en las especies afines al 'linaloe', B. aloexylon (Schiede ex Schlecht.) Engl.. 187 records from Mollusca specimens of Kuroshio Biological Research Foundation. 1560 records from UNM Earth Sciences Collection (Arctos). 55 records from New records of ant species from Yunnan, China. 250 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 1825 records from Caracterización biológica en la Serranía de San Lucas 2015. 1315 records from Bird specimens of Komatsu City Museum. 1 records from First occurrence of Anacroneuria singularis Righi-Cavallaro & Lecci, 2010 (Plecoptera: Perlidae) in Rondônia, western Amazonia, Brazil. 2 records from Description of larva of Euphaea superba Kimmins, 1936 (Odonata: Zygoptera: Euphaeidae) from China. 2 records from Cacoplistes (Laminogryllus) brevisparamerus sp. nov., a new species of Cachoplistinae (Orthoptera: Phalangopsidae) from Guangxi, China. 3 records from Description and life cycle of the hydrozoan Hydractinia uniformis, sp. nov. (Cnidaria: Hydrozoa: Hydractiniidae), from the coast of southeastern Brazil. 203 records from Collection Crustacea - ZSRO. 12 records from On the spider genus Syspira Simon, 1895 (Araneae: Miturgidae) in the Caribbean: four new species from Dominican Republic. 13 records from Three new species of moth flies (Diptera, Psychodidae, Psychodinae) from the Afrotropical Region. 8 records from Three new species of the genus Neuquenaphis (Hemiptera, Aphididae, Spicaphidinae) from southernmost South America. 10 records from Two new species of Ankareus Kerremans (Coleoptera: Buprestidae: Haplostethinae) from southern Africa. 1 records from Key to species of the genus Pachymetopius Matsumura (Hemiptera: Cicadellidae: Stegelytrini) with description of a new species from China. 6 records from Cambarus (C.) appalachiensis, a new species of crayfish (Decapoda: Cambaridae) from the New River Basin of Virginia and West Virginia, USA. 11 records from Dysaphis (Dysaphis) kadyrovi sp. nov. — a new aphid species (Hemiptera: Aphididae) from Tajikistan. 152 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 700 records from (Appendix B) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene sediments of DSDP Hole 94-610A from the North Atlantic. 901 records from (Appendix A) Pollen and spore counts at DSDP Hole 64-480. 12 records from A systematic appraisal of the types of ten species of Otostigmus (Parotostigmus) (Scolopendromorpha, Scolopendridae, Otostigminae). 3 records from Revision of the genus Allometopon Kertész (Diptera: Clusiidae). 21 records from Four new species of the genus Diaphorus (Diptera: Dolichopodidae) from China. 36169 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 26728 records from Museu_Paraense_Emílio_Goeldi _--_Ophidia_Collection. 94 records from Review of selected species of Campsurus Eaton 1868 (Ephemeroptera: Polymitarcyidae), with description of eleven new species and a key to male imagos of the genus. 18 records from Integration of molecular, bioacoustical and morphological data reveals two new cryptic species of Pelodytes (Anura, Pelodytidae) from the Iberian Peninsula. 2 records from A new genus and species of Acaenitini (Hymenoptera, Ichneumonidae, Acaenitinae) from China. 151 records from Revision of the genus Odocnemis Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from Turkey, the Caucasus and Iran with observations on feeding habits. 2303 records from Benthic foraminifers of sediment core Svanic90_9004. 7 records from Microcambeva ribeirae sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new sarcoglanidine catfish from the Rio Ribeira do Iguape basin, southeastern Brazil.. 3 records from A new species of Angaeus from Malaysia with possible affinity to related genera within Stephanopinae (Araneae: Thomisidae). 139 records from Review of the genus Eburodacrys White, 1853 (Coleoptera: Cerambycidae: Cerambycinae). 15 records from Two new enigmatic species of the genus Merodon Meigen (Diptera: Syrphidae) from the north-eastern Middle East. 4 records from Two new species of Flavoperla (Plecoptera: Perlidae) from Shaanxi Province of China. 10 records from Revision of the spider crab genus Sargassocarcinus Ward, 1936 (Crustacea: Brachyura: Epialtidae). 2 records from Trockenhang Greinhartsberg Edelfingen. 1 records from Tag der Artenvielfalt BUND Kaiserslautern. 451 records from Caracterización biológica de la ventana de biodiversidad del Complejo Cenagoso de Zapatosa, Municipio de Chimichagua, Cesar, Colombia. 1 records from Nothrus biciliatus. 1470 records from National Taiwan Museum. 2 records from Arthropoden aus südostalpinen Höhlen.. 3 records from A new species of the alpheid shrimp genus Thuylamea Nguyên, 2001 (Crustacea: Decapoda: Caridea) from Yatsushiro Sea, Kyushu, Japan. 142081 records from NINA insect database. 8 records from Cirrhigaleus australis n. sp., a new Mandarin dogfish (Squaliformes: Squalidae) from the south-west Pacific.. 17 records from The Neotropical species of Clistopyga (Hymenoptera, Ichneumonidae, Pimplinae). Part II: the C. isayae species group, with the description of seven new species. 3 records from A new spider species of the genus Sudharmia from Sumatra, Indonesia (Araneae, Liocranidae). 9 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Daniel Piechowski. 67 records from Review of the subtribe Gyrophaenina Kraatz 1856 (Coleoptera: Staphylinidae: Aleocharinae: Homalotini) of Middle Asia, with emphasis on the fauna of Kazakhstan. 3 records from Immature stages of the genus Casignetus MacLeay, 1819 (Coleoptera: Lucanidae: Lucaninae). 40 records from (Supplementary Table 2) Estimates of bottom-water oxygenation at site GeoB11185-1. 448 records from Three new Eustala (Araneae, Araneidae) species from the Galápagos Islands (Ecuador). 100 records from orstom_macassar_corindon_1980. 20 records from Description of a new species of the genus Caeneressa from China, with a checklist of the genus (Lepidoptera: Erebidae). 45798 records from Lichen herbarium TRH, NTNU University Museum. 1 records from Höltigbaum. 11 records from First record of ectoparasitic ciliates, of genus Trichodina (Ciliophora: Trichodinidae) parasiting cultured Oranda Gold Fish (Carassius auratus auratus L.) in India. 61 records from A taxonomic revision of the catshark genus Holohalaelurus Fowler 1934 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae), with descriptions of two new species.. 69 records from A new East African genus of spirostreptid millipedes (Diplopoda, Spirostreptida, Spirostreptidae), with notes on their fungal ectoparasite Rickia gigas. 126 records from A revision of the endemic South African long-jawed ground spider genus Drassodella Hewitt, 1916 (Araneae: Gallieniellidae). 245 records from Distribution of planktic foraminifera (250-500 µm) of sediment core GIK17732-1. 2088 records from Actualización de la base de datos de helmintos parásitos de peces de agua dulce de México. 1 records from Zitadelle Berlin-Spandau (7b). 1 records from Crenicichla ploegi, a new species of pike-cichlid of the C. saxatilis group from the Rio Juruena and upper Rio Paraguai basins in Brazil, with an updated diagnosis and biogeographical comments on the group (Teleostei: Cichlidae). 3076 records from Distribución geográfica de las lagartijas partenogenéticas del género Aspidoscelis en México. 422 records from Diatom abundance measured on water bottle samples at station PS58/090-4. 3 records from Comparative phylogeography of bamboo bats of the genus Tylonycteris (Chiroptera, Vespertilionidae) in Southeast Asia. 10234 records from Collection entomologique Barthélémy. 2 records from A new Pararistolochia Hutch. & Dalziel (Aristolochiaceae) from the Beanka Tsingy (western Madagascar). 5 records from New genus of the subfamily Oscinellinae from Brazil (Diptera: Chloropidae). 2 records from Extending rarity: discovery of the rare braconine genus, Carinibracon van Achterberg (Hymenoptera: Braconidae) in the Oriental region with the description of a new species from south India. 7339 records from Base de datos de las pteridofitas del estado de Veracruz, México. 13653 records from Árboles de Chiapas: registro georreferenciado de los ejemplares depositados en el herbario de la Academia de Ciencias de California (CAS). 12 records from A contribution to the Mutillidae (Hymenoptera) of Hong Kong. 13621 records from ZFMK Orthopteroidea collection. 21019 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 2 records from A new Schistura from the Salween basin in western Yunnan (Teleostei: Nemacheilidae). 2076 records from (Appendix B2) Distribution of planktic foraminifera in ODP Hole 181-1125A east of New Zealand. 702 records from HSU Vertebrate Museum Reptile Collection. 2 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 18 records from Opheliidae (Annelida: Polychaeta) from the western Pacific islands, including five new species. 23 records from (Table 3) Distribution of some benthic foraminifera in ODP Hole 108-659A. 935 records from Avifauna de la reserva de la biosfera El Cielo, Tamaulipas, México. 10358 records from Census of the flora of Benin. 7 records from Additions to the Genus Phyllodesmium, with a Phylogenetic Analysis and its Implications to the Evolution of Symbiosis. 36 records from Nannofossil abundance of Hole 26-258. 5 records from New species of Tomocerus (Entomobryomorpha, Tomoceridae) with remarkable form of mucronal dorsal lamella. 15 records from The identity of Equatobursa, with proposal of new genus and species level synonymies (Hemiptera: Heteroptera: Heterogastridae). 22 records from Entomobrya (Collembola, Entomobryidae) for the Canary Islands. 7 records from A new species of the genus Phymorhynchus (Neogastropoda: Raphitomidae) from a hydrothermal vent in the Manus Back-Arc Basin. 60 records from Review of the genus Singilis Rambur, 1837 of North Africa and Iberian Peninsula (Coleoptera: Carabidae: Lebiini). 3 records from Loxosomella decorata n. sp., a new solitary entoproct from San Juan Island, WA, USA. 2 records from A new species of the genus Asthenara Förster, 1869 (Hymenoptera, Ichneumonidae) from Mexico with identification key. 38 records from Two new species of Maiestas Distant (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with a new record from Australia. 8 records from A new species of arboreal microteiid lizard of the genus Euspondylus (Gymnophtalmidae: Cercosaurinae) from the Andean slopes of central Peru with comments on Peruvian Euspondylus. 370 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Hole 115-710A. 133 records from The genus Haplodrassus Chamberlin, 1922 in the Mediterranean and the Maghreb in particular (Araneae: Gnaphosidae). 15 records from Description of new species of algal-boring Limnoria (Crustacea, Isopoda, Limnoriidae) from Japan and redescription of Limnoria segnoides Menzies, 1957 and L. nagatai Nunomura, 2012. 521 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Site 115-709. 12 records from Five new species of Spartaeus Thorell, 1891 from China (Araneae: Salticidae). 20 records from Provisional checklist of the Tettigonioidea (Insecta: Orthoptera) from São Tomé & Príncipe with taxonomic remarks, bioacoustical data and the description of new taxa. 145 records from An illustrated catalogue of the New Zealand marsh beetles (Coleoptera: Scirtidae). 282 records from Foraminifera abundance of sediment core MD81-LC03. 214 records from Museo de Historia Natural Universidad de Caldas - Colección de Vertebrados e Invertebrados - Lepidoptera. 15 records from Remarkable new Australian mothflies (Diptera, Psychodidae). 251 records from Caracterización biológica de la ventana de biodiversidad enclave Atuncela, municipio de Dagua, Valle del Cauca. 4565 records from Base de datos de las regiones prioritarias 113 y 120 en los municipios de Zirándaro y Coahuayutla, (Guerrero). 49 records from Nannofossil abundance of Hole 11-106B. 2 records from First report on Paratischeria from Asia (Lepidoptera: Tischeriidae). 3 records from Two new Brazilian species of Neapion Alonso-Zarazaga, 1990 subgenus Neotropion Alonso-Zarazaga, 1990 with a key to South American species (Brentidae: Apioninae). 96 records from Overview of the Anyphaenids (Araneae, Anyphaeninae, Anyphaenidae) spider fauna from the Chocó forest of Ecuador, with the description of thirteen new species. 48 records from A new species of Psilorhynchus (Teleostei: Psilorhynchidae) from the Ataran River Basin, Myanmar, with comments on the generic name Psilorhynchoides.. 13736 records from MfN - Mallophaga Collection. 2 records from Synchrotron micro-CT scanning leads to the discovery of a new genus of morphologically conserved echinoid (Echinodermata: Cassiduloida). 5262 records from Spider Mites Collection of Jean Gutierrez. 609 records from Collection botanique Mulon L. (BOUM). 114 records from Revision of the Central American and Mexican species of the Curtonotum murinum species complex (Diptera: Curtonotidae). 439 records from Implementación de la bioindicación en el Río Magdalena. 1 records from Redescription of the monotypic genus Cubacanthozomus (Schizomida: Hubbardiidae) and conservation status of its type-species. 362 records from The genus Sphecodes Latreille 1804 (Hymenoptera: Apoidea: Halictidae) in Central Asia. 718 records from Inventario florístico de las Cactáceas del estado de Tamaulipas, México. 275438 records from R. L. McGregor Herbarium Vascular Plants Collection. 26568 records from LiquenCAT: Banco de datos de los líquenes de Cataluña. 4 records from The first record of genus Gryllomorpha Fieber in Romania (Orthoptera: Gryllidae: Gryllomorphinae). 5 records from A new species of Astyanax Baird & Girard (Characiformes: Characidae) from the upper rio Araguaia, Central Brazil. 21 records from Cryptochrysa Freitas & Penny, a generic homonym, replaced by Titanochrysa Sosa & Freitas (Neuroptera: Chrysopidae). 20 records from Colección de Referencia de Poríferos del Museo de Ciencias de la Universidad El Bosque. 479 records from CBS Bacteria Database. 6 records from Description of Cephalotes specularis n. sp. (Formicidae: Myrmicinae) - the mirror turtle ant. 211 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/092-3. 20 records from Notes on the Stenus indubius group with descriptions of four new species from China (Coleoptera, Staphylinidae). 1860 records from Estudio poblacional del chano norteño, Micropogonias megalops y la curvina Golfina Cynoscion othonopterus (Gilbert) (Pisces: Sciaenidae), especies endémicas del Alto Golfo de California, México. 5 records from Description of a new subspecies of Talicada nyseus (Guérin-Méneville, 1843) from Hainan, China (Lepidoptera: Lycaenidae), with notes on the genus Talicada Moore, 1881. 23 records from Three new species of Pambolus (Braconidae: Pambolinae) from Mexico, with comments on the variation of P. oblongispina Papp. 8 records from A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae). 31 records from The Plecoptera of Panama. II. Two new species, one new country record, and additional locality records of Anacroneuria (Perlidae) from western Panama. 1 records from Ueber eine noch nicht beschriebene Nothrus-Art. 1 records from A new aberrant Doryctinae genus (Hymenoptera: Braconidae) from French Guiana. 317211 records from CAS Herpetology (HERP). 43165 records from Butler University Friesner Herbarium (BUT). 255225 records from Herbarium specimens of Herbiers Universitaires de Clermont-Ferrand (CLF). 4 records from Three new species of Psyrassa Pascoe, 1866 (Coleoptera, Cerambycidae, Cerambycinae). 3 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 731 records from An updated record of Gaden Robinson's collection of Macro-moths of Fiji and Rotuma. 7 records from Sangpradubina, an astonishing new mayfly genus from Thailand (Ephemeroptera: Leptophlebiidae: Atalophlebiinae). 3 records from A new species of Caligus Müller, 1785 (Copepoda: Siphonostomatoida: Caligidae) from coral reef plankton in the Mexican Caribbean. 38 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 1764 records from Arachnida of Costa Rica (INBio). 205 records from Occurrence of some antimalarial plants from Cameroon. 3148 records from Ross A. Layberry, Collection. 33 records from New gnathiid isopod crustaceans (Cymothoida) from Heron Island and Wistari Reef, southern Great Barrier Reef. 3 records from Tardigrada and Rotifera from moss microhabitats on a disappearing Ugandan glacier, with the description of a new species of water bear. 24 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 26 records from New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon. 8 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 247 records from Pollen analysis of sediment profile BLA00 from Blankensee. 1825 records from Galathea II, Danish Deep Sea Expedition 1950-52. 12497 records from NCSM Non-molluscan Invertebrates Collection. 111529 records from The AAU Herbarium Database. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 6 records from Two new species of deeper dwelling Apogon (Perciformes: Apogonidae) from Micronesia and South Pacific Ocean.. 8 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 1483 records from Sistematización de la Colección Entomológica Forestal del CENID-COMEF. 451 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 5895 records from Colecção Entomológica do Museu de História Natural de Maputo. 18 records from Three new species of Labomimus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from Taiwan, China, with an updated key for L. shibatai Sawada-group. 3 records from Three new species of Elachistidae (Lepidoptera: Gelechioidea) from India. 2215 records from Collection Polychaeta - ZSRO. 21 records from Consolidated Checklist of Hard Corals of the Genus Acropora Oken, 1815 (Scleractinia: Acroporidae) in North Borneo, East Malaysia. 1 records from A new species of Eumeces Wiegmann 1834 (Sauria: Scincidae) from Iran. 17 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 182 records from Nannofossil abundance of Hole 55-433. 1037 records from Tetranychus urticae literature occurrences in a predator-prey system: Phytoseiulus persimilis (Acari: Phytoseiidae) and Tetranychus urticae (Acari: Tetranychidae). 132 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 2 records from A new species of Isthmura (Caudata: Plethodontidae) from the montane cloud forest of central Veracruz, Mexico. 17 records from Three new species of Tridentella Richardson, 1905 (Isopoda: Cymothoida: Tridentellidae) from New Caledonia. 4 records from A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China. 4201 records from Gunma Museum of Natural History, Fungi Specimen. 12 records from Aves de la expedición en lago de Tota, Boyacá - Proyecto Boyacá BIO. 38293 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 61 records from Range table from benthic foraminifera in ODP Hole 199-1215B. 27 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 14392 records from Plant specimens of Horaiji-san Museum of Natural History Kichi T. collection. 3 records from Lectotypification of three species of Silene sect. Italicae (Rohrb.) Schischk. (Caryophyllaceae). 3 records from Three new species of the cutthroat eel genus Dysomma, with comments on the variation of D. taiwanense (Anguilliformes: Synaphobranchidae). 3 records from Three new species of Entomobryoidea (Collembola: Entomobryomorpha) from Brazilian Caatinga-Cerrado transition, with identification keys to Brazilian Cyphoderus, Pseudosinella and Trogolaphysa species. 5 records from Revision of Chimarrogale (Lipotyphla: Soricidae) from Vietnam with comments on taxonomy and biogeography of Asiatic water shrews. 4479 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 11 records from New records of deep-sea shrimps of family Solenoceridae Wood-Mason & Alcock, 1891 (Crustacea: Decapoda: Dendrobranchiata) from Southwestern Atlantic. 187017 records from UWFC Ichthyology Collection. 1 records from Morphological and molecular distinction of two Fridericia species (Clitellata, Enchytraeidae) having same spermatheca type. 35 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 22386 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 50 records from A new genus and species of the family Symphysanodontidae, Cymatognathus aureolateralis (Actinopterygii: Perciformes) from Indonesia. 91253 records from CUMV Fish Collection. 6922 records from MUST, Insecta. 57 records from Distribution of planktic foraminifera of sediment core GIK23400-3. 2116 records from Collection entomologique Pierre Lachiver. 50 records from Distribution of planktic foraminifera of sediment core PS1235-1 at stadium 5.5. 3 records from ZUEC-POP - Coleção de Polyplacophora do Museu de Zoologia da UNICAMP. 72389 records from University of Tennessee Fungal Herbarium. 4 records from Amphicnemis valentini sp. nov. from the Cardamom ecoregion in Cambodia and Vietnam (Odonata: Coenagrionidae). 164367 records from University of Michigan Museum of Zoology, Division of Mollusks. 2519 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 2103 records from Flora ficológica de la huasteca potosina. 5 records from Meschia zoui sp. nov., first representative of the family Meschiidae from China (Hemiptera: Heteroptera: Lygaeoidea). 1093 records from Systematic studies on Pseudomyrmex acacia-ants (Hymenoptera: Formicidae: Pseudomyrmecinae). 22 records from Lannapsyche and Marilia species of China (Trichoptera: Odontoceridae). 14 records from Niphargus dancaui sp. nov. (Amphipoda, Niphargidae) - a new species thriving in sulfidic groundwaters in southeastern Romania. 1 records from A new miniature Melanesian Forest Frog (Ceratobatrachidae: CORNufeR) from New Britain Island, constituting the first record of the subgenus BATRAchylOdes from outside of the Solomon Archipelago. 1347 records from Collection Crustacea ZMG. 2000 records from Fish specimens of Takatsuki Nature Museum (Aquapia Akutagawa). 10098 records from Araneae Collection. 1 records from A fossil caddisfly (Insecta: Trichoptera) from the Eocene of Colorado. 228 records from Biodiversidad acuática del río Amacuzac, Morelos, México. 4 records from Description of Coladenia simianensis sp. nov. (Lepidoptera: Hesperiidae) from China, with an annotated checklist of the genus Coladenia Moore, 1881. 70 records from Neotropical spittlebugs related to Neaenini (Hemiptera, Cercopidae) and the origins of subfamily Cercopinae. 169 records from Recursos hidrobiológicos de Caño Cristales, La Macarena, Meta. 225150 records from Limnic freshwater benthic invertebrates biogeographical mapping/inventory NTNU University Museum. 326 records from Mamíferos de los Parques Nacionales Lagunas de Montebello y Palenque, Chiapas. 187 records from Philinidae, Laonidae and Philinorbidae (Gastropoda: Cephalaspidea: Philinoidea) from the northeastern Pacific Ocean and the Beaufort Sea (Arctic Ocean). 90 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 13661 records from HPL - Herbário do Jardim Botânico Plantarum. 438 records from Caracterización biológica de la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 3174 records from Family Primulaceae in Virtual Herbaria of CSBG SB RAS (NSK). 1 records from Description of a second species of the genus Moronius Grossi & Vaz-de-Mello, 2015 (Coleoptera: Scarabaeidae: Rutelinae: Rutelini). 775 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 3945 records from TTRS Ornithology. 3 records from Stadtpark Herzberg (Elster). 1 records from Unser Schulhof - eine Apotheke. 8 records from Description of a new alpheid shrimp, Automate isabelae sp. nov. (Decapoda, Caridea, Alpheidae) found in fish stomach contents of the lane snapper Lutjanus synagris (Linnaeus, 1758), from the west coast of Florida, Gulf of Mexico. 1 records from Chance, luck and a fortunate finding: a new species of watersnake of the genus Helicops Wagler, 1828 (Serpentes: Xenodontinae), from the Brazilian Pantanal wetlands. 731 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 7245 records from Sammmlung Ule Brasilien Herbarium Hamburgense HBG. 1 records from Berlin - Treptower Park / Karpfenteich. 3 records from First record of the genus Echthronomas Forster, 1869 (Hymenoptera, Ichneumonidae, Campopleginae) for the fauna of Ukraine. 15 records from Taxonomy of European Damaeidae (Acari: Oribatida) I. Kunstidamaeus Miko, 2006, with comments on Damaeus sensu lato. 8276 records from El género Bursera en México. Parte II. 103 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 323-U1341. 464 records from PSUZC-Mammal Collection. 4 records from Two new marine species of Cocconeis (Bacillariophyceae) from the west coast of Sweden. 6323 records from Canadian National Collection of Insects. 4 records from First description of the female of the spider Savignia zero Eskov, 1988 (Araneae: Linyphiidae). 4 records from The Cephenniini of China. IX. Cephennomicrus Reitter of Yunnan (Coleoptera: Staphylinidae: Scydmaeninae). 70 records from Distribution of hydropolyp species in surface sediments of the Red Sea (Table 5). 33 records from Two new species of Epimelitta Bates from Brazil and a new synonymy in Stenopseustes Bates (Coleoptera, Cerambycidae, Cerambycinae, Rhinotragini). 361 records from (Appendix 5) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2039. 40992 records from Museu Paraense Emílio Goeldi - Diptera Collection. 1 records from Hoplophora straminea. 114757 records from Herbarium Senckenbergianum (FR). 142306 records from Invertebrate Zoology Division, Yale Peabody Museum. 35 records from Six new species of Stenometopiini (Hemiptera: Cicadellidae: Deltocephalinae) with redescription of additional species and new distributional records. 1 records from Zetes cespitum. 71 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Ross Sea (Antarctica) collected by the New Zealand Antarctic expedition BioRoss 2004 with RV Tangaroa. 40914 records from Managing West African Bees in the implementation of a first reference collection: Bees caught in three areas of Burkina Faso. 144 records from SDSM Botany and Paleobotany Collections. 364 records from Pollen profile 1 from Richland Creek. 12995 records from Mammalia Collection of Institute of Systematics and Evolution of Animals. 29 records from CHAS Ichthyology Collection (Arctos). 16 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas III. Suctobelbella alloenasuta n. sp. und Suctobelbella messneri n. sp. sowie die bisher aus der DDR bekannten Arten der nasalis-subtrigona-Gruppe (Suctobelbidae). 102 records from Sipuncula collection of National Museum of Nature and Science. 4 records from A new member of the genus Isotomurus from the Kuril Islands (Collembola: Isotomidae): returning to the problem of “ colour pattern species ”. 935 records from Biodiversidad de moluscos opistobranquios (Mollusca: Opisthobranchiata), del Pacífico mexicano: Isla Cedros-Vizcaíno. 60 records from Nine new species of Agromyzidae from North Carolina, USA, with new host and distribution records for additional species. 1 records from Pottundkopp. 8 records from Pairs in copulation of the highly dimorphic genus Pristocera Klug (Hymenoptera, Bethylidae) from Madagascar solve taxonomic problems of male-female associations. 503 records from Mamíferos: Colección Universidad de Caldas. 15714 records from Catálogo de insectos de la colección del Centro de Entomología. 9 records from Luciobarbus lanigarensis and L. numidiensis, two new species of barbels from the Mediterranean Sea basin in North Africa (Teostei: Cyprinidae). 15593 records from Bryophyte specimens of Nagano Environmental Conservation Research Institute, Nagano Prefecture. 753 records from Estudio taxonómico de las aves y mamíferos del Valle Cuatrociénegas, Coahuila, México. 293 records from Catalogue of Coleoptera type specimens housed in the collection of the Museu de Ciências Naturais, Fundação Zoobotânica do Rio Grande do Sul, Brazil. 62177 records from LSUMZ Bird Tissues. 4441 records from Canadian Museum of Nature Palaeobotany Collection. 6 records from On the taxonomy of the genus Barsochrista Singh & Kirti, 2016 (Lepidoptera, Erebidae, Arctiinae). 33 records from Revision of the genus Coeliccia Kirby in Borneo part II: Two new species from the membranipes- group, with a redescription of C. macrostigma Laidlaw (Odonata: Zygoptera: Platycnemididae). 20992 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 25534 records from SP-Fungi - Maria Eneyda Pacheco Kauffmann Fidalgo. 3110 records from IFO Filamentous Fungi. 110 records from DAYO: Invasive Alien Reptiles in the Philippines. 14866 records from Mollusca specimens of Okinawa Prefectural Museum & Art Museum. 28796 records from MPM Herpetology. 96 records from Catalogue of Notomastus M. Sars, 1851 (Annelida, Capitellidae) and the description of a new species from the Gulf of California. 78283 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 989 records from Diversidad de los mamíferos de la Reserva de la biósfera Tehuacán-Cuicatlán, Puebla-Oaxaca, México. 34 records from Species of Horismenus Walker (Hymenoptera: Eulophidae) associated with bruchid beetles (Coleoptera: Chrysomelidae: Bruchinae), including five new species. 3 records from The Vietnamese population of Megophrys kuatunensis (Amphibia: Megophryidae) represents a new species of Asian horned frog from Vietnam and southern China. 127902 records from Australian National Wildlife Collection provider for OZCAM. 8276 records from HUSC - Herbário Unisanta. 3 records from A new genus, Protaustrosimulium, for four species of Australian black flies (Diptera: Simuliidae). 11926 records from Crispin S. Guppy Collection. 54 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 9 records from Polyrhachis (Myrma) cyaniventris F. Smith, 1858 (Hymenoptera: Formicidae) and a related new ant species from the Philippines.. 7693 records from NHM, Heteroptera. 688 records from Algae, Norwegian College of Fishery Science. 34 records from Revision of the subgenus Stigmatodipogon Ishikawa of the genus Dipogon Fox (Hymenoptera: Pompilidae: Pepsinae). 118 records from The genus Stactobia McLachlan (Trichoptera, Hydroptilidae) in Japan. 1054 records from Plantas de la cuenca alta y media del río Bita, Vichada (Colombia). 1 records from A new shrimp species of the genus Lebbeus White, 1847 (Crustacea: Deacpoda: Caridea: Thoridae) from a deep-sea cold seep site off southwestern Taiwan. 166879 records from Lund Museum of Zoology - Insect collections (MZLU). 27 records from Review of the plant bug genus Fingulus Distant in Indochina (Hemiptera: Heteroptera: Miridae: Deraeocorini), with descriptions of two new species. 6 records from Two new Chinese species of Tomocerus at different stages of troglomorphic adaptation (Collembola, Tomoceridae). 1365183 records from Australian Museum provider for OZCAM. 1 records from On the Chilopoda from Turkey. 2 records from A new genus of Pulaeini (Acari: Prostigmata: Cunaxidae) from South-East Asia. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 337 records from Phytoplankton samples - 2001/02 V3 CLIVAR. 14 records from Description of the female of Labena madoricola González-Moreno & Bordera, 2015 (Hymenoptera, Ichneumonidae, Labeninae), with new records of Labena species from Mexico. 1 records from Record of genus Xestophrys Redtenbacher, 1891 (Orthoptera: Tettigoniidae: Conocephalinae; Copiphorini) and description of one new species from India. 32 records from Black fungus gnats (Diptera: Sciaridae) of Queensland, Australia. Part I. Genera Chaetosciara Frey, Corynoptera Winnertz, Cratyna Winnertz, Epidapus Haliday, Keilbachia Mohrig, Lobosciara Steffan, Phytosciara Frey and Scatopsciara Edwards. 6 records from On the genus Hirsutopes Pajni, 1990, (Coleoptera: Curculionidae, Entiminae), with the description of a new species. 471 records from Phytoplankton data collected from a diurnal station in Sevastopol Bay (Black Sea) during 1952. 90 records from Herbario MAIA, colección de Ericas del INIA-CIFOR. 10 records from African Spilogona Schnabl: morphology of the male terminalia and description of a new species (Diptera: Muscidae). 5638 records from Estación Biológica Doñana - CSIC, Aves. 52 records from Fossil butterflies, calibration points and the molecular clock (Lepidoptera: Papilionoidea). 10 records from Five new species of genus Encarsia Förster from China (Hymenoptera: Aphelinidae). 260 records from osac_oarisma. 174666 records from Vascular plant herbarium, Tromsø Museum. 26 records from Terre d'huiles. 14165 records from NYSM Mammals. 7 records from Lost species in Cameroon: rediscovery of the endangered freshwater crab, Louisea balssi (Bott, 1959) (Brachyura: Potamonautidae), with notes on its ecology and conservation. 2067 records from Base de datos de la familia Cactaceae de la Península de Baja California, México. 37839 records from Fiocruz/CEIOC - Coleção Entomológica do Instituto Oswaldo Cruz. 57909 records from JPB - Herbário Lauro Pires Xavier. 61925 records from Canadian Museum of Nature Fish Collection. 166 records from A revision of the spider genus Zaitunia (Araneae, Filistatidae). 6 records from On four new species of the jumping spider genus Mago O. Pickard-Cambridge, 1882 from South America (Araneae: Salticidae). 130 records from Endemic earthworms (Oligochaeta: Lumbricidae) of the Balkan Peninsula: a review. 8 records from Pomacentrus aurifrons, a new species of damselfish (Pomacentridae) from Melanesia.. 5042 records from Tracheophyta collection of Biodiversity Center of Japan, Ministry of the Environment. 1 records from Wiese und Bach am Kleinen Eutiner See (Eutin). 10 records from Sand wasp (Hymenoptera: Crabronidae) parasites emerging from mud wasp nests (Hymenoptera: Sphecidae) - a reliable host record of Thraxan Yeates & Lambkin (Diptera: Bombyliidae: Anthracinae) with description of the pupal exuviae of three Thraxan species. 115756 records from Field Museum of Natural History (Botany) Bryophyte Collection. 11 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-083BX. 31173 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 14 records from What is Pseudopotamilla reniformis (Sabellidae)? Comparisons of populations from Britain, Iceland and Canada with comments on Eudistylia and Schizobranchia. 336 records from Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia). 16 records from Resurrection of Caltoris ranrunna (Sonan) from synonymy as a skipper endemic to Taiwan based on COI barcode and morphology. 29 records from A review of the arboreal Afrotropical ant genus Axinidris.. 24 records from Bombus impatiens Cresson (Hymenoptera: Apidae, Apinae, Bombini) from the Prairies Ecozone in Canada. 29 records from Smear slide analysis on sediment core GeoB4223-2. 99300 records from Landesmuseum Kärnten. 268 records from Biodiversidad en las propuestas para declaratoria de Áreas Protegidas en los Municipios de Dagua, Restrepo, La Cumbre y Vijes y un Grupo de Reservas Naturales de la Sociedad Civil. 1 records from Arthropoden aus südotsalpinen Höhlen gesammelt von Karl Strasser. 4. Aufsatz. 3 records from Taxonomy of the Sand Sliders of Western Australia’s central coast (genus Lerista, Squamata: Scincidae): recognition of Lerista miopus (Günther, 1867). 2450 records from Plantas de la expedición al Río Apaporis - Proyecto Colombia BIO. 24 records from Nannofossil abundance of Hole 26-250. 4 records from New species and records of the Pericoma trifasciata group from Croatia (Diptera: Psychodidae). 2 records from Studies on the ant fauna of Melanesia V. The tribe Odontomachini.. 2382 records from Bay of Fundy Species List. 445 records from Pollen analysis of sediment profile BLA0 from Blankensee. 3 records from Revision of the genus Celebargiolestes Kennedy, 1925 (Odonata: Argiolestidae). 11 records from Notes on the Rhyacophila angulata Species Group with descriptions of two new species (Insecta, Trichoptera, Rhyacophilidae). 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 9 records from Study of Laemostenus species across Zagros and Central zone of Iran, with the description of seven new cavernicolous species and notes on subgenus Iranosphodrus (Coleoptera: Carabidae: Sphodrini). 88 records from Revision of the genera Pareuthria Strebel, 1905, Glypteuthria Strebel, 1905 and Meteuthria Thiele, 1912 (Gastropoda: Buccinulidae) with the description of three new genera and two new species from Southwestern Atlantic waters. 10 records from Integrative taxonomy reveals two sympatric species of the genus Eucriotettix Hebard, 1930 (Orthoptera: Tetrigidae). 557 records from Composition of the coccolith flora in sediment core K708-007. 89470 records from UPCB - Herbário do Departamento de Botânica. 11 records from A new species of Probolomyrmex from Madagascar.. 5 records from Notes on the genus Yunnantettix Zheng (Tetrigidae: Cladonotinae), with descriptions of two new species from Thailand. 2 records from A revision of the genus Conocrinus d’Orbigny, 1850 (Echinodermata, Crinoidea, Rhizocrinidae) and its place among extant and fossil crinoids with a xenomorphic stalk. 1017 records from Poliquetos invasores (Annelida: Polychaeta) del Puerto de Mazatlán, Sinaloa. 9 records from Lethrus (Lethrus) thracicus (Coleoptera: Geotrupidae), a new species from the European part of Turkey. 44 records from Contributions to the taxonomy, identification, and biogeography of the Western Palaearctic species of Campoletis Förster (Ichneumonidae: Campopleginae). 7357 records from ZFMK Coleoptera collection. 278 records from MfN - Fossil invertebrates IIa. 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 82 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 8 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 251 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 13064 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 93619 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 3 records from Description of a new species of Andaeschna (Odonata: Aeshnidae) from the Western Colombian Andes. 139 records from A new western Canadian record of Epeoloides pilosulus (Cresson). 4837 records from Free-living marine Nematodes from San Antonio and Cormoranes sandy beaches (Rio Negro, Argentina), 2006.. 6 records from A revision of Holothuria (Halodeima) kefersteinii (Selenka, 1867) and the revival of Holothuria inornata Semper, 1868 from sea cucumbers collected in Mexico and Central America. 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 26681 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv). 39 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 8 records from New species of grasshopper genus Aptoceras Bruner, 1908 (Orthoptera, Acrididae, Ommatolampidinae, Ommtolampidiini) from Iguaçu National Park (Southern Brazil), including a taxonomic key and distribution data. 51 records from Review of the Nearctic genus Scyletria Bishop & Crosby (Araneae, Linyphiidae), with a transfer of S. jona to Mermessus O. Pickard-Cambridge. 227 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 2 records from Contributions to the palaeofauna of Ptinidae (Coleptera) known from Baltic amber. 173415 records from Hymenoptera specimen database of Kyushu University. 3428 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 16 records from A new western Canadian record of Epeoloides pilosulus (Cresson), with discussion of ecological associations, distribution and conservation status in Canada. 343 records from Distribution of planktic foraminifera (250-500 µm) of sediment core GIK23059-3. 2097 records from Finnish Floristic Database (Literature Sources). 174 records from The Myriapoda Collection of the National Museum of Nature and Science. 27 records from Review of the genus Elasmostethus (Hemiptera: Heteroptera: Acanthosomatidae) from the Korean Peninsula. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 11472 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 2 records from A new species of anole from Parque Nacional Volcán Arenal, Costa Rica (Reptilia, Squamata, Dactyloidae: Norops). 7 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 8406 records from Conservatoire Botanique Pierre Fabre. 7 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 92 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 3 records from А new species of Alona Baird, 1843 (Cladocera: Chydoridae) from the ancient Lake Ohrid. 1309 records from Mongolian Plant (MMNH-PL). 2 records from Description of Penia mantillerii sp. nov. (Coleoptera: Elateridae: Dimini), with a key to Penia species from Vietnam and nearby areas. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 136 records from Nannofossil abundance of Hole 39-359. 46 records from A check list of the Chinese Zeugophorinae (Coleoptera: Megalopodidae), with new synonym, new record and two new species of subgenus Pedrillia from China. 71 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 80 records from An updated checklist of Iranian Encyrtidae (Hymenoptera, Chalcidoidea). 152 records from Nannofossil abundance of Hole 49-412. 33 records from Coeliccia rolandorum sp. nov. from eastern Cambodia and southern Vietnam, the eastern relative of C. kazukoae Asahina, 1984 (Odonata: Platycnemididae). 4 records from A new species of Lamprodila (Ovalisia Kerremans, 1900) (Coleoptera: Buprestidae) from Sulawesi, Indonesia. 8 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 35 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 995 records from Amphibian specimens of Kanagawa Prefectural Museum of Natural History. 1594 records from Musée Vert ornithology collection. 18 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 896 records from Coleção de Ictiologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 20 records from Nine new Trechisibus species from Peru and Argentina (Coleoptera: Carabidae: Trechinae). 89 records from A review of the genus Potemnemus Thomson, 1864 (Coleoptera: Cerambycidae) with description of a new species from Papua New Guinea. 35897 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 61798 records from Fiocruz/CMN - Coleção de Mosquitos Neotropicais. 2 records from Porifera ZMK. 1 records from Nothrus furcatus. 4 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 17 records from A new species of Victrix Staudinger, 1879 from Kazakhstan (Lepidoptera, Noctuidae). 12 records from Redescription and lectotype designation of Chasmogenus abnormalis (Sharp), with notes on its distribution. 56 records from Revision of the genus Tmesiphorus LeConte, 1849 (Coleoptera: Staphylinidae: Pselaphinae) from Japan. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 1 records from Oribates flammula. 97134 records from University of Tennessee Bryophyte Herbarium. 11001 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 9726 records from Paleobotany Specimens. 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 219 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 11 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 106100 records from Fish (NSMK-PI). 3 records from One new species and new record of the leafhopper genus Watara Dworakowska from Thailand (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini). 10 records from Collection Myriapoda - SNSD. 55 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 1924 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 1 records from On two italian Lithobius species described by Silvestri with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda Lithobiidae). 30 records from Lacantunia enigmatica (Teleostei: Siluriformes) a new and phylogenetically puzzling freshwater fish from Mesoamerica.. 5 records from Description of the male of Phoebe ornator (Tippmann, 1960) (Coleoptera: Cerambycidae: Lamiinae: Hemilophini), analysis of the species biogeography, and first observation of chromatic gender dimorphism in Hemilophini. 78 records from Geographical and bathymetric distribution of mysids (Crustacea: Mysida) in the seas of the Iberian Peninsula. 9 records from Morphological and molecular analyses confirm the occurrence of two sympatric Lysmata shrimp (Crustacea, Decapoda) in the southwestern Atlantic. 50 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 15 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 1 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 363 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 3 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 2 records from The discovery of Euryrhynchidae (Crustacea: Decapoda) in India, with the description of a new genus and species. 8 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 3974 records from DBL_Life. 4 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 859 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 4 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 95 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 6 records from Systematic account of new Porifera (Demospongiae) records from the oceanic Island of Madeira (NE Atlantic). 3 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura: Diogenidae) from southern India. 2171 records from Thrips (Thysanoptera) in Norway. 3 records from A new species of Homo from the Late Pleistocene of the Philippines. 2 records from Deux nouvelles espèces d’ Aloe L. (Xanthorrhoeaceae, Asphodelaceae), section Lomatophyllum Rowley, de Madagascar. 613 records from Implementación de la bioindicación en el Río Cauca - 2016. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 104 records from BID-Malawi-Arctiidae-Biodiversity-Data. 89 records from Bird specimens of Ryukyu University Museum (Fujukan). 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 2 records from A new species of Eupariini from Eocene Baltic amber (Coleoptera: Scarabaeidae: Aphodiinae). 211 records from Nannofossil abundance of Hole 67-497. 34 records from The Moroccan species of Chyromyidae (Diptera) with descriptions of five new species of Aphaniosoma Becker. 74123 records from IAN herbarium - Embrapa Amazônia Oriental - Herbário Virtual REFLORA. 526 records from FernsDarwinCore. 3 records from Überall ist Wunderland. 4269 records from Colección de hongos del Herbario "Jaime Andrés Rodríguez". LEB-Fungi. 10 records from A new diploid species belonging to the Odontophrynus americanus species group (Anura: Odontophrynidae) from the Espinhaço range, Brazil. 5 records from Note on the genus Lecanophryella (Ciliophora: Suctorea) with description of a new species from west coast of India. 24 records from A Gondwanan concept of Simplimorpha Scoble (sensu lato): a step toward clarity in the generic diagnostics of global Nepticulidae (Lepidoptera). 5 records from Revision of the genus Sinobathyscia Perreau (Coleoptera, Leiodidae, Cholevinae) from China, with description of a new species. 19 records from Revision of the Greater Antilles genus Paratrikona Spaeth, 1923 (Coleoptera: Chrysomelidae: Cassidinae: Dorynotini). 481 records from (Appendix B) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-966B. 54 records from Nannofossil abundance of Hole 49-409. 73 records from Taxonomic review of the species of Helina R. - D. (Diptera: Muscidae) from Andean-Patagonian forests. 2 records from Two new species of Amphinemura (Plecoptera: Nemouridae) from Tibet. 1 records from A new species of Cyphocarididae (Crustacea, Amphipoda, Lysianassoidea) from off the northeastern Brazilian coast. 8 records from Dolichopus nimbatus Parent, 1927 revisited, with two new synonyms (Diptera: Dolichopodidae). 28468 records from Actualización de la base de datos del estado de Morelos de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 24 records from (Table 1) Chemical composition of segregations and groundmass seperates of ODP Leg 135 samples. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 120 records from Pollen profile 2 from Richland Creek. 13162 records from Observations du Conservatoire botanique national du Bassin parisien.. 177 records from Echinodermata specimens of Kuroshio Biological Research Foundation. 3426 records from Fossil Birds. 110350 records from TNHC Herpetology Collection. 89 records from ZUEC-POR - Coleção de Porifera do Museu de Zoologia da UNICAMP. 110 records from Inventario de la biota terrestre (florístico) y marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel. 4681 records from Museu Darder de Banyoles. 2 records from Two new species of Acontias (Acontinae, Scincidae) from the Mpumalanga Highveld escarpment of South Africa. 316 records from Moss species from Heard Island, 1987 and 2000. 818 records from floraregional_2da. 289 records from Odonata del Museo de Entomología de la Universidad del Valle. 1421 records from Geochemistry and sedimentology on core POS200/10_6-2. 146 records from Colección de moldes endocraneanos del CENPAT. 20 records from Biting midges of the tribe Ceratopogonini (Diptera: Ceratopogonidae) from the Middle East, with keys and descriptions of new species. 7 records from The larva and pupa of Potamyia flavata (Banks 1934) (Trichoptera: Hydropsychidae): Description, life cycle, and notes on its biology. 1 records from Hornmilben (Oribatida) [pages 261 to 322]. 2 records from Contribution to the genus Okinawepipona Yamane (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 54 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 2 records from Re-evaluation of the morphology of the monotypic genera Lycastonereis Rao, 1981 and Ganganereis Misra, 1999 (Annelida, Phyllodocida, Nereididae). 1121 records from Collection Meebold HBG Herbarium. 239 records from Hidden in plain sight: reassessment of the pig-footed bandicoot, Chaeropus ecaudatus (Peramelemorphia, Chaeropodidae), with a description of a new species from central australia, and use of the fossil record to trace its past distribution. 7 records from Cyphocharax boiadeiro, a new species from the upper rio Araguaia, Amazon basin, Brazil (Characiformes: Curimatidae). 1 records from First fossil Eccoptarthridae (Coleoptera: Curculionoidea) from the Mesozoic of China. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 3 records from First description of the male of the easternmost Harpactea species, H. parthica (Araneae: Dysderidae). 30952 records from SANT-Algae. 843 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 9 records from Hyleina kaphetea, a new genus and species of clearwing moths from tropical Africa (Lepidoptera: Sesiidae: Sesiini). 1262 records from (Appendix B) Abundance of dinoflagellates in sediment core MD01-2378. 29 records from Systematics, ecology and distribution of the mygalomorph spider genus Cteniza Latreille, 1829 (Araneae, Mygalomorphae, Ctenizidae). 5917939 records from International Barcode of Life project (iBOL). 2 records from Loneura Navás (Psocodea: Psocomorpha: Ptiloneuridae): new species from Brazil, and description of the female of Loneura maracaensis Garcia Aldrete, with a checklist of all known species of the genus. 4 records from Lectotype designation and distribution updates on the freshwater shrimp species Atyaephyra stankoi Karaman 1972. 205 records from Japan Collection of Microorganisms(Basidio). 22 records from MtDNA differentiation and taxonomy of Central Asian racerunners of Eremias multiocellata - E. przewalskii species complex (Squamata, Lacertidae). 2 records from Synaptus iranicus sp. nov., a second species of the genus Synaptus Eschscholtz, 1829 from Iran (Coleoptera: Elateridae) discovered by an integrative approach. 5 records from Amphibia, Bokermannohyla nanuzae, Scinax curicica, Leptodactylus camaquara, Physalaemus evangelistai, and Proceratophrys cururu: Distribution extensions. 3 records from A new species of and a new transfer from the millipede genus Polydrepanum Carl, 1932 (Polydesmida, Paradoxosomatidae, Polydrepanini). 43 records from Abundance of coccosphere-units of sediment core GIK23424-3. 1 records from Flora. 6 records from Free-living marine nematodes of Desmodorella and Zalonema (Nematoda: Desmodoridae) with description of two new species from the deep sea of the North Western Pacific. 58 records from Undercover speciation of wentletraps (Caenogastropoda: Epitoniidae) in the Southwestern Atlantic. 14 records from Re-description of Coeliccia erici Laidlaw, and the description of Coeliccia sameerae sp. nov. from Peninsular Malaysia (Odonata: Zygoptera: Platycnemididae). 3 records from Argiope hoiseni, a new species of the spider genus Argiope (Araneae, Araneidae) from Peninsular Malaysia based on morphology and molecular analyses. 8 records from Reconsideration of the apterous carventine genus Crassocoris and description of Paracrassocoris gen. nov. from China (Hemiptera: Heteroptera: Aradidae). 3652 records from La flora útil de dos comunidades indígenas del Valle de Tehuacán-Cuicatlán: Coxcatlán y Zapotitlán de las Salinas, Puebla. 14 records from Collection Amphibia fossil SMF. 58451 records from Collection Mollusca SMF. 10 records from Two new records of the coral symbiont crab genus Quadrella Dana, 1851, from Taiwan, with notes on the taxonomy of Q. boopsis Alcock, 1898 (Crustacea: Brachyura: Trapeziidae). 12681 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleobotany National Collection (BAPb). 4 records from A new species of Decimiana Uvarov from Brazil, with updated key to species and remarks on their geographic distribution (Mantodea: Acanthopidae, Acanthopinae). 4 records from hips of Epidrepanus within the subtribe Drepanocerina (Coleoptera: Scarabaeidae: Scarabaeinae: Oniticellini), with the description of two new species. 1289 records from Records of the Victorian Conservation Seedbank. 54 records from Revision of the genus Lamprima Latreille, 1804 (Coleoptera: Lucanidae). 119366 records from The digitization of plant specimens of NTU. 4 records from Carcinoplax fasciata, a new species of deep-water goneplacid crab from southwestern India (Crustacea: Decapoda: Brachyura: Goneplacoidea). 851 records from (Table 3) Distribution of calcareous nannofossils at DSDP Site 82-563 in the North Atlantic. 554 records from Dinoflagellate abundance in sediment core JM06-WP-04-MCB. 2 records from Aphaenogaster gamagumayaa sp. nov.: the first troglobiotic ant from Japan (Hymenoptera: Formicidae: Myrmicinae). 8259 records from Insect specimens of Okinawa Prefectural Museum & Art Museum. 2 records from Orientatractis brycini sp. nov. (Nematoda: Atractidae) from characiform freshwater fishes in Gabon, Africa. 38 records from (Supplement Table 5) Percentage cover abundance of plants recorded at the Primary Site on Disko Island. 8 records from Three new minute leaf litter beetles discovered by citizen scientists in Maliau Basin, Malaysian Borneo (Coleoptera: Leiodidae, Chrysomelidae). 5 records from Two new littoral species of the genus Anurida Laboulbène, 1865 (Collembola, Neanuridae) from the Pacific coast of Asia. 1897 records from Royal BC Museum - Herpetology Collection. 5 records from Two new and one newly recorded species of Polypedilum Kieffer 1912 with DNA barcodes from Oriental China (Chironomidae: Diptera). 5426 records from Collection Francaise de Bacteries Phytopathogenes. 2805 records from Fundación Miguel Lillo - Colección Mamíferos. 7918 records from University of Alberta Museum of Zoology Ornithology Collection (UAMZ). 1614 records from New Brunswick Museum Collection. 23 records from The world species of Ophthalmothrips Hood (Thysanoptera; Phlaeothripidae), with new records from Africa, China and Japan. 29 records from New dark species of the bee genus Colletes (Hymenoptera, Colletidae) from Mexico and Guatemala. 20 records from Taxonomic revision of Brazilian genus Tyrannoseira Bellini & Zeppelini, 2011 (Collembola, Entomobryidae, Seirinae). 10 records from A mountain of millipedes VI. New records, new species, a new genus and a general discussion of Odontopygidae from the Udzungwa Mts, Tanzania (Diplopoda, Spirostreptida, Odontopygidae). 6202 records from Lichens of North-Eastern Poland. 33 records from Morphological differences between Stenocionops furcatus (Olivier, 1791) and S. coelatus (A. Milne-Edwards, 1878) (Crustacea, Decapoda, Brachyura, Majoidea). 6 records from Exogoninae (Annelida: Syllidae) from Chilean Patagonia. 1310925 records from Paleobiology Database. 3509 records from Entocytheridae (Ostracoda) World Database. 74 records from Taxonomy and Biogeography without frontiers – WhatsApp, Facebook and smartphone digital photography let citizen scientists in more remote localities step out of the dark. 25 records from Cochlostoma revised: the subgenus Lovcenia Zallot et al., 2015 (Caenogastropoda, Cochlostomatidae). 119 records from Pycnogonida collection from the Museu Nacional de História Natural e da Ciência da Universidade de Lisboa, Portugal. 108 records from Studies in Hawaiian Diptera I: New Distributional Records for Endemic Asteia (Asteiidae). 11 records from Description of the first Caribbean Oscarellidae (Porifera: Homoscleromorpha). 138529 records from flora&fauna(NIBR)2019. 1001 records from Naturhistorisches Museum Mainz, Botanical Collection. 4 records from Ameisen von Madagaskar, den Comoren und Ostafrika.. 1793 records from Herbarium BSG Lichenes. 6 records from Rhigonema naylae n. sp. (Rhigonematomorpha: Rhigonematidae) a new parasitic nematode from a Japanese polydesmid millipede (Polydesmida: Xystodesmidae). 3 records from First record of the genus Eriopisella Chevreux, 1920 (Crustacea, Amphipoda, Senticaudata, Eriopisidae) from Australia, with the description of a new species, Eriopisella moretoni sp. nov.. 5253 records from Colección de Laurales, Liliales, Lycopodiales, Magnoliales y Malpighiales del Museo Botánico CORD - IMBIV. 32 records from Two new species of Nullana from southern Brazil (Hemiptera: Cicadellidae: Gyponini) with key to males. 26 records from Shallow-water Ascidians from Matua Island (central Kuril Islands, NW Pacific). 2227 records from IRAD Cameroon insect collection. 4310 records from MfN - Fossil vertebrates V. 13 records from On a collection of deep-water shrimp (Crustacea, Decapoda) from the Dutch Caribbean, with the description of a new species of Pseudocoutierea. 30 records from Averages and ranges of paleoenvironmental proxy records of ODP Hole 108-658C (Table 1). 463 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 209 records from Nannofossil abundance of Hole 94-610B. 2 records from New ichneumonids (Hymenoptera, Ichneumonidae) from the Eocene Tadushi Formation, Russian Far East. 12 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 374 records from Medicinal potential of African plants (Togo). 91 records from Phytoseiid mites (Acari: Phytoseiidae) associated with tropical ornamental plants, with a checklist and a key to the species of Bahia, Brazil. 8330 records from Nijmegen Natural History Museum (NL) - Herbarium. 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 10738 records from The Suguru Igarashi Insect Collection (Lepidoptera: Lycaenidae) of The University Museum, The University of Tokyo. 12557 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 7 records from First records of Glaresidae (Coleoptera) in China, with the description of a new species from Inner Mongolia and Shaanxi. 23 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 26 records from Genus Bungona Harker, 1957 (Ephemeroptera: Baetidae) from China, with descriptions of three new species and a key to Oriental species. 955 records from Vertebrados terrestres de San Juan de Camarones, Durango. 142 records from Botanical collection of the National Museum. 24 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 303 records from National Botanic Garden Belgium - Martius. 43 records from The megisthanid mites (Mesostigmata: Megisthanidae) of Australia. 20084 records from Colección de Solanales del Museo Botánico CORD - IMBIV. 8328 records from Actualización de las bases de datos de las colecciones de plantas vasculares y macromicetos del herbario de la UJAT. 218 records from West African pholcid spiders: an overview, with descriptions of five new species (Araneae, Pholcidae). 11 records from A new species of Dicrotendipes (Diptera: Chironomidae) from Florida. 11 records from The genus Cylloepus Erichson, 1847 (Coleoptera: Elmidae: Elminae) new species and combinations. 1 records from A new species of Bathynomus Milne Edwards, 1879 (Isopoda: Cirolanidae) from The Bahamas, Western Atlantic. 282 records from (Table 2) Distribution of some benthic foraminifera in ODP Hole 108-658A. 7 records from A new crayfish of the genus Cambarus Erichson, 1846 (Decapoda: Cambaridae) from an under-sampled habitat type in central Ten- nessee, USA. 1 records from Myolaimus ibericus sp. n. (Nematoda, Rhabditida, Myolaimidae) from southern Iberian Peninsula, with a key to species of the genus. 3326 records from Plant specimens of Nasunogahara Museum. 9400 records from Colección de Mamíferos del Instituto Alexander von Humboldt. 2 records from New species of the Genus Haliclona (Haplosclerida: Chalinidae) from Korea. 854 records from Análisis de Integridad Biológica en la Reserva Forestal Protectora Regional Bitaco. Convenio CVC- Univalle 108 de 2017. 450 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 6729 records from Epibenthos and demersal fish monitoring at long-term monitoring stations in the Belgian part of the North Sea. 4591 records from WII Herbarium Dataset. 1889 records from Diatomeas bentónicas de los oasis de Baja California Sur. 26309 records from Quaid-i-
Keywords: GBIF; biodiversity; species occurrences